Compositions of cellulose ester and ethylene vinyl acetate, and articles made using these compositions

JP2025029019APending Publication Date: 2025-03-05EASTMAN CHEM CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024207859
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-09-27
Filing Date
2024-11-29
Publication Date
2025-03-05

AI Technical Summary

Benefits of technology

【0022】 【0022】幾つかの態様においては、セルロースエステル樹脂は、2.5未満の相対粘度を有する少なくとも1つのセルロースプロピオネート(CP)、セルロースブチレート(CB)、セルロースアセテートプロピオネート(CAP)、セルロースアセテートブチレート(CAB)、セルロースアセテートイソブチレート(CAIB)、セルロースプロピオネートブチレート(CPB)、セルローストリプロピオネート(CTP)、又はセルローストリブチレート(CTB)から選択される。幾つかの態様においては、セルロースエステル樹脂は、2.5より低い相対粘度を有する個々のグレードであってよく、或いはより高い相対粘度(即ち2.5より高い)を有する1以上のグレード及び2.5未満の相対粘度を有する少なくとも1つのグレードを有するセルロースエステルのブレンドであってよい。一態様においては、セルロースエステル樹脂は、より高い相対粘度(即ち2.5より高い)を有する1以上のグレード及びより低い相対粘度(即ち2.5未満)を有する少なくとも1つのグレードを有するセルロースエステルのブレンドであってよく、このブレンドによって2.5より低い平均相対粘度がもたらされる。相対粘度は、アセトン中の2%のセルロースエステル溶液に関して求められ、25℃の温度において測定される。幾つかの態様において、セルロースエステルが2.5未満の相対粘度を有する場合には、セルロースエステル組成物/樹脂は、より高い相対粘度を有するセルロースエステル組成物と比べて同等のTgにおいて減少した溶融粘度(又は増加した溶融流動性)を有し得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029019000001
    Figure 2025029019000001
  • Figure 2025029019000002
    Figure 2025029019000002
  • Figure 2025029019000003
    Figure 2025029019000003
Patent Text Reader

Abstract

To provide melt-processable cellulose ester compositions.SOLUTION: A cellulose ester composition is provided comprising at least one cellulose ester, at least one ethylene vinyl acetate copolymer, and optionally at least one plasticizer. Also provided are processes for producing the cellulose ester compositions, and articles made using these compositions, such as eyeglass frames, automotive parts, and toys.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001]

[0001] The present invention is in the field of cellulose ester chemistry, particularly cellulose esters comprising ethylene vinyl acetate (EVA) copolymers and, optionally, a plasticizer. The present invention is also in the field of cellulose ester compositions comprising at least one EVA copolymer and, optionally, at least one plasticizer. Also provided are methods of making these cellulose ester compositions, as well as plastic articles made with these compositions, such as eyeglass frames, automobile parts, and toys. [Background technology]

[0002]

[0002] Cellulose ester compositions usually have a heat distortion temperature (HDT) or glass transition temperature (Tg) of less than 90°C. Commercially available cellulose esters that are melt processed into articles usually contain a significant amount of plasticizer to allow processing and provide sufficient toughness to the molded article. However, adding a plasticizer has disadvantages because it reduces the HDT compared to the base cellulose ester, limiting the use of the cellulose ester material to applications that can accept a HDT below about 90°C. Also, cellulose ester molded articles can experience exudation of the plasticizer during use.

[0003]

[0003] It has been proposed to blend certain EVA copolymers with certain cellulose esters to eliminate the need for low molecular weight plasticizers. However, the combinations proposed so far have been limited to certain relatively low molecular weight cellulose esters to provide acceptable processability and melt flow for molding applications. As a result, the use of such materials is limited for higher temperature end uses and higher impact toughness applications. Summary of the Invention [Problem to be solved by the invention]

[0004] It would be beneficial to provide a melt-processible cellulose ester composition that did not have these drawbacks. [Means for solving the problem]

[0005]

[0005] Surprisingly, it has been found that compositions of cellulose esters such as cellulose acetate propionate and cellulose acetate butyrate can be produced that have a glass transition temperature (Tg) of greater than 120°C and good transparency and toughness. In some embodiments of the present invention, this can be achieved by reducing the amount of plasticizer, and in some embodiments, by completely eliminating the use of plasticizer in the composition. By eliminating plasticizer, the general problems associated with the exudation of plasticizer during use can be eliminated. However, reducing or eliminating plasticizer can reduce the toughness of these high Tg cellulose compositions. Surprisingly, it has been found that certain EVA copolymers can restore the toughness of high Tg cellulose-based compositions and provide cellulose ester compositions with good flow properties and good transparency that are suitable for higher temperature applications and maintain dimensional stability for long periods of time.

[0006] In some embodiments, the present invention relates to dispersing an EVA copolymer in a cellulose ester composition in an amount sufficient to improve the mechanical and physical properties of the cellulose ester composition. The EVA copolymer modified cellulose esters according to some embodiments of the present invention are melt processable and are commercially available plasticized cellulose esters. It has the unique property of having a significantly higher Tg than plastic resins, and has a high elastic modulus, good impact properties, and good resistance to deformation under load.

[0007]

[0007] In one aspect of the present invention, there is provided a cellulose ester composition comprising at least one cellulose ester, at least one ethylene vinyl acetate (EVA) copolymer, and optionally at least one plasticizer. In one aspect, the relative viscosity of the cellulose ester is greater than 6.0 as measured at 25°C for a 2% by weight cellulose ester in acetone solution, and the cellulose ester composition has a Tg of at least 120°C.

[0008] In another aspect of the present invention, there is provided a cellulose ester composition comprising at least one cellulose ester, and at least one EVA copolymer, and at least one plasticizer.

[0009]

[0009] In another aspect of the present invention, a method for producing a cellulose ester composition is provided, comprising contacting at least one cellulose ester, at least one EVA copolymer, and optionally at least one plasticizer, and mixing the combination. In one aspect, the plasticizer is present in an amount that does not substantially reduce the Tg of the cellulose ester composition compared to a similar composition without the plasticizer. In some embodiments, the Tg does not change (e.g., decrease) by more than 10%, or more than 5%, or more than 2% as a result of the inclusion of the plasticizer.

[0010]

[0010] In some embodiments of the present invention, there is described a cellulose ester composition which does not contain a plasticizer but contains 1 wt % to 35 wt %, or 2.5 wt % to 30 wt %, or 10 to 30 wt % of an EVA copolymer based on the total weight of the cellulose ester composition, and has a Tg value greater than 120°C and a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m.

[0011]

[0011] In another aspect of the present invention, a plasticizer-free melt-processable cellulose ester composition is provided. In some embodiments, the melt-processable cellulose ester composition comprises 1% to 35%, or 2.5% to 30%, or 10 to 30% by weight of EVA copolymer based on the total weight of the cellulose ester composition, and has a Tg value greater than 120°C, a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m, and a spiral flow value of at least 38 centimeters (15 inches) measured at a barrel temperature of 240°C using the procedure described herein.

[0012]

[0012] In another aspect of the present invention, the melt-processable cellulose ester composition comprises 2 wt% to 20 wt%, or 5 wt% to 15 wt% of an EVA copolymer, based on the total weight of the cellulose ester composition, and has a Tg value greater than 120°C, a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m, and a viscosity of less than 10,000 P at 230°C and 100 rad / sec.

[0013]

[0013] In other embodiments, the melt-processable cellulose ester compositions described above can include some plasticizer. In some embodiments, the plasticizer is present in an amount that does not substantially reduce the Tg of the cellulose ester composition compared to a similar composition without the plasticizer. In some embodiments, the Tg does not change (e.g., decrease) by more than 10%, or more than 5%, or more than 2% as a result of the inclusion of the plasticizer.

[0014]

[0014] In one aspect of the present invention, there is described a melt-processable cellulose ester composition comprising 15 wt% or less of a plasticizer, or 10 wt% or less of a plasticizer; comprising 1 wt% to 35 wt%, or 2.5 wt% to 30 wt%, or 10 to 30 wt% of an EVA copolymer; having a Tg value greater than 120°C; and having a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m.

[0015]

[0015] In another aspect of the present invention, there is described a melt-processable cellulose ester composition comprising 15 wt% or less of a plasticizer, or 10 wt% or less of a plasticizer, based on the total weight of the cellulose ester composition; comprising 1 wt% to 35 wt%, or 2.5 wt% to 30 wt%, or 10 to 30 wt% of an EVA copolymer, based on the total weight of the cellulose ester composition; having a Tg value greater than 120°C; having a notched Izod impact strength value greater than 100 J / m; and having a spiral flow value of at least 38 centimeters (15 inches) measured at a barrel temperature of 240°C using the procedures described herein.

[0016]

[0016] In another aspect of the present invention, there is described a melt-processable cellulose ester composition comprising 15 wt% or less of a plasticizer, or 10 wt% or less of a plasticizer, based on the total weight of the cellulose ester composition; comprising 1 wt% to 35 wt%, or 2.5 wt% to 30 wt%, or 10 to 30 wt% of an EVA copolymer, based on the total weight of the cellulose ester composition; having a Tg value greater than 120°C; having a notched Izod impact strength value greater than 100 J / m; and having a viscosity of less than 10,000 P at 230°C and 100 rad / sec.

[0017]

[0017] In one aspect of the present invention, there is provided a polymer-based resin comprising at least one cellulose ester, at least one EVA copolymer, and optionally at least one plasticizer, wherein the cellulose ester is CAP, and the resin comprises 0-5 wt%, 0-2 wt%, or 0-1 wt% of plasticizer. In one aspect, the cellulose ester is CAP, and the resin comprises no plasticizer. In one aspect, the cellulose ester is CAP, the EVA is unmodified, and the resin comprises no plasticizer and less than 5 wt%, or less than 2 wt% of any other additives.

[0018]

[0018] In another aspect of the present invention, there is provided a cellulose ester composition comprising at least one cellulose ester, at least one EVA copolymer, and optionally at least one plasticizer, the cellulose ester being CAB and comprising 0-5 wt%, 0-2 wt%, or 0-1 wt% of plasticizer. In one aspect, the cellulose ester is CAB and the resin is free of plasticizer. In one aspect, the cellulose ester is CAB, the EVA is unmodified, the resin is free of plasticizer, and comprises less than 5 wt%, or less than 2 wt% of any other additives.

[0019] In some embodiments, the cellulose ester resin is selected from at least one of cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose acetate isobutyrate (CAIB), cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB). In some embodiments, the resin contains or does not contain less than 25% by weight, or less than 20% by weight, or less than 15% by weight, or less than 10% by weight, or less than 5% by weight of any other polymer or polymers that contribute to the continuous binder phase of the resin and the cellulose ester. For example, EVA is present as a dispersed phase in the cellulose ester resin and does not contribute to the continuous binder phase of the resin and the cellulose ester.

[0020] In some embodiments, the cellulose ester resin is selected from at least one of cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose acetate isobutyrate (CAIB), cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB), and has a relative viscosity higher than 6.0. In some embodiments, the cellulose ester resin may be an individual grade with a relative viscosity higher than 6.0, or may be a blend of cellulose esters with one or more grades with a lower relative viscosity (i.e., <6.0) and at least one grade with a higher relative viscosity (i.e., >6.0). In one embodiment, the cellulose ester resin may be a blend of cellulose esters having one or more grades with a lower relative viscosity (i.e., <6.0) and at least one grade with a higher relative viscosity (i.e., >6.0), resulting in an average relative viscosity greater than 6.0. The relative viscosity is determined for a 2% cellulose ester solution in acetone and measured at a temperature of 25°C.

[0021] In some embodiments, the cellulose ester having a relative viscosity higher than 6.0 can be selected from cellulose acetate butyrate containing about 15 to about 57% by weight of butyryl based on the total weight of the polymer.In some embodiments, the cellulose ester having a relative viscosity higher than 6.0 can be selected from cellulose acetate propionate containing about 15 to about 52% by weight of propionyl based on the total weight of the polymer.

[0022] In some embodiments, the cellulose ester resin is selected from at least one of cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose acetate isobutyrate (CAIB), cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB) having a relative viscosity of less than 2.5. In some embodiments, the cellulose ester resin can be an individual grade having a relative viscosity of less than 2.5, or a blend of cellulose esters having one or more grades having a higher relative viscosity (i.e., higher than 2.5) and at least one grade having a relative viscosity of less than 2.5. In one embodiment, the cellulose ester resin can be a blend of cellulose esters having one or more grades having a higher relative viscosity (i.e., higher than 2.5) and at least one grade having a lower relative viscosity (i.e., less than 2.5), which results in an average relative viscosity of less than 2.5. Relative viscosity is determined for a 2% cellulose ester solution in acetone and measured at a temperature of 25° C. In some embodiments, when the cellulose ester has a relative viscosity of less than 2.5, the cellulose ester composition / resin may have a reduced melt viscosity (or increased melt flow) at a comparable Tg compared to a cellulose ester composition having a higher relative viscosity.

[0023] In some embodiments, the cellulose ester is a cellulose acetate propionate (CAP) having a propionyl content of greater than 15% by weight based on the total weight of the polymer. In some embodiments, the cellulose ester is a cellulose acetate propionate (CAP) having a propionyl content of greater than 49% (propionic acid content of greater than 66%) based on the total weight of the CAP polymer. In some embodiments, the cellulose ester is a cellulose acetate propionate (CAP) having a propionyl content of less than 38% (propionic acid content of less than 50%) based on the total weight of the CAP polymer.

[0024] In some embodiments, the cellulose ester is, based on the total weight of the polymer, In some embodiments, the cellulose ester is a cellulose acetate butyrate (CAB) having a butyryl content of greater than 15% by weight based on the total weight of the CAB polymer. In some embodiments, the cellulose ester is a cellulose acetate butyrate (CAB) having a butyryl content of greater than 40% (greater than 50% butyric acid content) based on the total weight of the CAB polymer. In some embodiments, the cellulose ester is a cellulose acetate butyrate (CAB) having a butyryl content of less than 32% (less than 40% butyric acid content) based on the total weight of the CAB polymer, or a butyryl content ranging between 15-32% by weight. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] In one aspect of the present invention, there is provided a cellulose ester composition comprising at least one cellulose ester, at least one EVA copolymer, and optionally at least one plasticizer.

[0026] In some embodiments, the cellulose ester used in the present invention has a sufficient content of C3 to C 10 Any cellulose ester having an acid salt or ester group may be used. The cellulose esters that can be used for the present invention generally have the structure:

[0027] [ka]

[0028] (In the formula, R 1 , R 2 , and R 3 are independently selected from the group consisting of hydrogen or straight chain alkanoyl having 2 to 10 carbon atoms. Repeat units of 1.0 to 1.5.0. For cellulose esters, the substitution level is usually expressed as the degree of substitution (DS), which is the average number of non-OH substituents per anhydroglucose unit (AGU). Generally, conventional cellulose contains three hydroxyl groups in each AGU unit that can be substituted; therefore, the DS can have a value between 0 and 3. However, low molecular weight cellulose mixed esters may have a total degree of substitution slightly higher than 3 due to the contribution of end groups. Natural cellulose is a large polysaccharide with a degree of polymerization of 250 to 5,000 even after pulping and purification, so the assumption that the maximum DS is 3.0 is almost correct. However, as the degree of polymerization decreases, such as in low molecular weight cellulose mixed esters, the end groups of the polysaccharide backbone become relatively more significant, which results in a DS that can range above 3.0. Low molecular weight cellulose mixed esters are discussed in more detail below in this specification. Since DS is a statistical average, a value of 1 does not indicate that all AGUs have a single substituent. In some cases, there may be unsubstituted anhydroglucose units, some with two and some with three substituents, and usually this value is a non-integer. Total DS is defined as the average number of all substituents per anhydroglucose unit. The degree of substitution per AGU may also refer to a specific substituent, such as hydroxyl, acetyl, butyryl, or propionyl.

[0029] In some embodiments, the cellulose ester used may be a cellulose triester or a secondary cellulose ester. Examples of cellulose triesters include: Examples of secondary cellulose esters include, but are not limited to, cellulose tripropionate or cellulose tributyrate. Examples of secondary cellulose esters include cellulose acetate propionate and cellulose acetate butyrate.

[0030] In one embodiment of the present invention, the cellulose ester can be selected from cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose propionate butyrate (CPB), cellulose acetate isobutyrate (CAIB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB), or the like, or combinations thereof. Some examples of cellulose esters are described in U.S. Patents 1,698,049; 1,683,347; 1,880,808; 1,880,560; 1,984,147; 2,129,052; and 3,617,201 (all of which are incorporated herein by reference to the extent that they do not contradict the statements herein). In one embodiment, the cellulose ester is CAP.

[0031]

[0029] In one embodiment of the present invention, the cellulose ester can be selected from cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose acetate isobutyrate (CAIB), cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB), but is not selected from cellulose acetate (CA).

[0032] In some embodiments, the cellulose ester has a relative viscosity (η) of greater than 6.0 to about 9.0, or from about 6.1 to about 8.5, measured at a temperature of 25° C. for a 2% by weight solution of the cellulose ester in acetone. rel). The relative viscosity is the ratio of the flow time of the polymer solution to the solvent in which the polymer is dissolved. The relative viscosity according to the present invention can be determined as follows. Using a capillary type viscometer (CANNON mini PV-HX), measure the relative viscosity of the sample according to ASTM-D4603. Examples of cellulose esters include, but are not limited to, cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose acetate isobutyrate (CAIB), cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB).

[0033] In some embodiments of the present invention, the cellulose ester comprises, by weight, 15-52%, or 20-52%, or 25-52%, or 30-52%, or 35-52%, or 40-52%, or 45-52%, or 49-52%, or 15-50%, or 20-50%, or 25-50%, or 30-50%, or 35-50%, or 40-50%, or 45-50%, or 15 to less than 50%, or 20 to less than 50%, or 25 to less than 50%, based on the total weight of the cellulose ester polymer. or less than 30-50%, or less than 35-50%, or less than 40-50%, or less than 45-50%, or less than 35-50%, or less than 40-50%, or less than 45-50%, or less than 35-50%, or less than 40-50%, or less than 45-50%, or 15-38%, or 20-38%, or 25-38%, or 30-38%, or 35-38%, or 15-35%, or 20-35%, or 25-35%, or 30-35%, or 15-30%, or 20-30%, or 25-30%.

[0034] In some embodiments of the present invention, the cellulose ester comprises from 15 to 57%, or from 20 to 57%, or from 25 to 57%, or from 30 to 57%, or from 35 to 57%, or from 40 to 57%, or more than 40%, by weight, based on the total weight of the cellulose ester polymer. <57%, or 41-57%, or 45-57%, or 50-57%, or 15-55%, or 20-55%, or 25-55%, or 30-55%, or 35-55%, or 40-55%, or more than 40% up to 55%, or 41-55%, or 45-55%, or 50-55%, 15-50%, or 20-50%, or 25-50%, or 30-50%, or 35-50%, or 40-50%, or more than 40% up to 50%, or 41-50%, or has a total percentage of butyryl in the range of 45-50%, or 15-45%, or 20-45%, or 25-45%, or 30-45%, or 35-45%, or 40-45%, or greater than 40% up to 45%, or 41-45%, or 15-35%, or 20-35%, or 25-35%, or 30-35%, or 15% to less than 32%, or 20% to less than 32%, or 25% to less than 32%, or 15-30%, or 20-30%, or 25-30%.

[0035] In some embodiments, the cellulose ester is present in an amount, as a percentage of the total weight of the polymer, of from 15% to 55%, or from 15% to 50%, or from 15% to 45%, or from 15% to 40%, or from 15% to 35%, or from 15% to 30%, or from 15% to 25%, or from 15% to 20%, or from 20% to 55%, or from 20% to 50%, or from 20% to 45%, or from 20% to 40%, or from 20% to 35%, or from 20% to 30%, or from 20% to 25%, or from 25% to 55%, or from 25% to 50%, or from 25% to 45%, or from 25% to 40%, or from 25% to 35%, or from 25% to 30%, or The cellulose propionate butyrate or cellulose acetate propionate butyrate has a total propionate and butyryl content in the range of 30% to 55%, or 30% to 50%, or 30% to 45%, or 30% to 40%, or 30% to 35%, or 35% to 55%, or 35% to 50%, or 35% to 45%, or 35% to 40%, 40% to 55%, or 40% to 50%, or 40% to 45%, or 40% to 55%, or 40% to 55%, or 40% to 55%, or 40% to 45%, or 45% to 55%, or 45% to 50%, or 50% to 55%.

[0036] The cellulose esters can be prepared by any method known in the art. Examples of methods for preparing cellulose esters can be found in Kirk-Othmer, Encyclopedia of Chemical Technology, 5th edition, vol.5, Wiley-Interscience, New York (2004), pp.394-444. The cellulose can be obtained in different grades and sources, such as from cotton linters, softwood pulp, hardwood pulp, corn fiber, and other agricultural raw materials, and bacterial cellulose, among others.

[0037]

[0035] One method for producing cellulose esters is the esterification of cellulose by mixing it with an appropriate organic acid, an acid anhydride, and a catalyst. The cellulose is then converted to a cellulose triester. The ester is then hydrolyzed by adding a water-acid mixture to the cellulose triester, which can then be filtered to remove gel particles or fibers. Water is then added to the mixture to precipitate the cellulose ester. The cellulose ester can then be washed with water to remove reaction by-products, followed by dehydration and drying.

[0038] The cellulose triester to be hydrolyzed may have three substituents independently selected from alkanoyl having 2 to 10 carbon atoms. Examples of cellulose triesters include cellulose triacetate, cellulose tripropionate, and cellulose tributyrate, or mixed triesters of cellulose such as cellulose acetate propionate and cellulose acetate butyrate. These cellulose esters can be prepared by a number of methods known to those skilled in the art. For example, cellulose esters can be prepared by heterogeneous acylation of cellulose in a mixture of a carboxylic acid and an anhydride in the presence of a catalyst such as H2SO4. The triesters can also be prepared by homogeneous acylation of cellulose dissolved in a suitable solvent such as LiCl / DMAc or LiCl / NMP.

[0039] After esterification of cellulose to the triester, a portion of the acyl substituents can be removed by hydrolysis or alcoholysis to give secondary cellulose esters. As mentioned above, depending on the particular method used, the distribution of the acyl substituents can be random or non-random. Secondary cellulose esters can also be produced directly without hydrolysis by using a limited amount of acylating reagent. This process is particularly useful when the reaction is carried out in a solvent that dissolves cellulose. All of these methods produce the cellulose esters useful in the present invention.

[0040]

[0038] Most commonly, commercial secondary cellulose esters are prepared by firstly acid-catalyzed heterogeneous acylation of cellulose to form cellulose triesters. After obtaining a homogeneous solution of cellulose triesters in the corresponding carboxylic acid, the cellulose triesters are then subjected to hydrolysis until the desired degree of substitution is obtained. After isolation, random secondary cellulose esters are obtained, i.e., the relative degree of substitution (RDS) at each hydroxyl is approximately equal.

[0041] Some examples of cellulose esters useful in the present invention can be prepared using techniques known in the art and are available from Eastman Chemical Company, Kingsport, Tenn., USA, such as Eastman® Cellulose Acetate Propionate. CAP482-20, Eastman® Cellulose Acetate Propionate CAP141-20 , Eastman® Cellulose Acetate Butyrate CAB381-20, and Cellulose Acetate butyrate CAB171-15. Examples of some common cellulose esters are shown in Table 1 below with the relative viscosity values ​​shown. In some embodiments, common cellulose esters having a relative viscosity higher than 6.0 (as shown in Table 1) can be used in the present invention. In some other embodiments, combinations of different common cellulose esters having a relative viscosity higher than or lower than 6.0 (as shown in Table 1) can be used.

[0042]

[0040]

[0043] [Table 1]

[0044] In some embodiments, cellulose esters having a relative viscosity of less than 6.0 (e.g., as shown in Table 1) can be used. In some other embodiments, a combination of different common cellulose ester grades can be used, with grades having a relative viscosity higher than 6.0 and grades having a relative viscosity lower than 6.0 (e.g., as shown in Table 1). In some embodiments including cellulose esters having a relative viscosity lower than 6.0 and EVA copolymers, the cellulose ester compositions can be provided for applications requiring a Tg higher than 120°C, or higher than 130°C, or higher than 140°C; and an Izod impact value lower than 150 J / m, or lower than 125 J / m, or lower than 100 J / m. In some other embodiments, including cellulose esters with a relative viscosity of less than 6.0 and EVA copolymers, the cellulose ester compositions can provide for applications requiring higher melt flow (or lower melt viscosity) than those using cellulose esters with Tg greater than 100° C., or greater than 110° C., or greater than 120° C.; and higher relative viscosity, in which case the cellulose ester composition further comprises a type and amount of plasticizer discussed herein. In one embodiment, the plasticizer is of a type that is primarily, substantially, or entirely contained in the EVA copolymer discontinuous phase of the cellulose ester composition and not (except possibly in minor amounts) contained in the continuous cellulose ester polymer continuous phase.

[0045] In some embodiments, cellulose esters having a relative viscosity of less than 2.5 can be used. In some other embodiments, a combination of different cellulose ester grades can be used, with a grade having a relative viscosity of less than 2.5 and a grade having a relative viscosity of more than 2.5. In some embodiments, including a cellulose ester having a relative viscosity of less than 2.5 and an EVA copolymer, the cellulose ester composition can be provided for applications requiring a lower melt viscosity (or higher melt flowability) than cellulose esters having a Tg of more than 120°C, or more than 130°C, or more than 140°C; and a higher relative viscosity.

[0046] In some embodiments, the cellulose esters used in the present invention may also contain chemical functional groups, which are referred to herein as either derivatized, modified, or functionalized cellulose esters. A functionalized cellulose ester is a cellulose ester that is Free hydroxyl groups can be produced by reacting with a bifunctional reactant that has one linking group for grafting to cellulose ester and one functional group for providing new chemical groups to cellulose ester. Examples of such bifunctional reactants include succinic anhydride, which is linked by an ester bond to provide acid functionality; mercaptosilane, which is linked by an alkoxysilane bond to provide mercapto functionality; and isocyanatoethyl methacrylate, which is linked by a urethane bond to provide methacrylate functionality.

[0047] In one aspect of the invention, functionalized cellulose esters are prepared by reacting the free hydroxyl groups of a cellulose ester with a difunctional reactant to produce a cellulose ester having at least one functional group selected from the group consisting of unsaturation (double bond), carboxylic acid, acetoacetate, acetoacetate imide, mercapto, melamine, and long alkyl chain.

[0048]

[0045] Bifunctional reactants for preparing cellulose esters containing unsaturated (double bond) functional groups are described in U.S. Patents 4,839,230; 5,741,901; 5,871,573; 5,981,738; 4,147,603; 4,758,645; and 4,861,629 (all of which are incorporated herein by reference to the extent that they do not contradict the statements herein). In one embodiment, cellulose esters containing unsaturation are prepared by reacting cellulose esters containing residual hydroxyl groups with acrylic compounds and m-isopropienyl-α,α'-dimethylbenzyl isocyanate. Grafted cellulose esters are urethane-containing products with pendant (meth)acrylate and α-methylstyrene groups. In another embodiment, the cellulose ester containing unsaturation is prepared by reacting maleic anhydride with a cellulose ester in the presence of a catalyst of an alkaline earth metal or ammonium salt of a lower alkyl monocarboxylic acid and at least one saturated monocarboxylic acid having from 2 to 4 carbon atoms. In another embodiment, the cellulose ester containing unsaturation is prepared from the reaction product of (a) at least one cellulose polymer having isocyanate-reactive hydroxyl functionality and (b) at least one hydroxyl-reactive poly(α,β-ethylenically unsaturated) isocyanate.

[0049]

[0046] Bifunctional reactants for preparing cellulose esters containing carboxylic acid functionality are described in U.S. Patents 5,384,163; 5,723,151; and 4,758,645, all of which are incorporated herein by reference to the extent that they do not contradict the statements herein. In one embodiment, the cellulose esters containing carboxylic acid functionality are prepared by reacting a cellulose ester with a mono- or diester of maleic or fumaric acid, thereby obtaining a cellulose derivative with double bond functionality. In another embodiment, the cellulose esters containing carboxylic acid functionality have a first and a second residue, the first residue being a residue of a cyclic dicarboxylic anhydride, and the second residue being a residue of a lipophilic monocarboxylic acid and / or a residue of a hydrophilic monocarboxylic acid. In yet another embodiment, the cellulose esters containing carboxylic acid functionality are cellulose acetate phthalates, which can be prepared by reacting cellulose acetate with phthalic anhydride.

[0050]

[0047] Bifunctional reactants for preparing cellulose esters containing acetoacetate functionality are described in U.S. Patent 5,292,877, which is incorporated herein by reference to the extent that it does not contradict the teachings herein. In one embodiment, the cellulose esters containing acetoacetate functionality are prepared by reacting (i) cellulose; (ii) diketene, alkyl acetoacetate, 2,2,6-trimethyl-4H-1,3-dioxin-4-one, or mixtures thereof; and (iii) lithium chloride with a carboxamide selected from the group consisting of 1-methyl-2-pyrrolidinone, N,N-dimethylacetamide, or mixtures thereof. a solubilizing amount of a solvent system comprising:

[0051]

[0048] Bifunctional reactants for preparing cellulose esters containing acetoacetate imide functional groups are described in U.S. Patent 6,369,214, which is incorporated herein by reference to the extent that it does not contradict the teachings herein. Cellulose esters containing acetoacetate imide functional groups are the reaction products of cellulose esters and amine-functional compounds containing at least one acetoacetyl group and at least one primary amine.

[0052]

[0049] The bifunctional reactant for preparing cellulose ester containing mercapto functional group is described in US Patent 5,082,914 (incorporated herein by reference to the extent that it does not contradict the description herein).In one aspect of the present invention, cellulose ester is grafted with silicon-containing thiol component, which can be commercially available or prepared by procedures known in the art.Examples of silicon-containing thiol compounds include, but are not limited to, (3-mercaptopropyl)trimethoxysilane, (3-mercaptopropyl)-dimethyl-methoxysilane, (3-mercaptopropyl)dimethoxymethylsilane, (3-mercaptopropyl)dimethylchlorosilane, (3-mercaptopropyl)dimethylethoxysilane, (3-mercaptopropyl)diethoxymethylsilane, and (3-mercaptopropyl)triethoxysilane.

[0053]

[0050] Bifunctional reactants for preparing cellulose esters containing melamine functional groups are described in U.S. Patent 5,182,379 (incorporated herein by reference to the extent that they do not contradict the statements herein). In one embodiment, the cellulose esters containing melamine functional groups are prepared by reacting a cellulose ester with a melamine compound to form a grafted cellulose ester in which the melamine groups are grafted to the backbone of the anhydroglucose rings of the cellulose ester. In one embodiment, the melamine compound is selected from the group consisting of methylol ethers of melamine and aminoplast resins.

[0054]

[0051] Bifunctional reactants for preparing cellulose esters containing long alkyl chain functional groups are described in US Patent 5,750,677 (incorporated herein by reference to the extent that they do not contradict the statements herein). In one embodiment, cellulose esters containing long alkyl chain functional groups are prepared by reacting cellulose in a carboxamide diluent or urea diluent with an acylating agent using a titanium-containing species. The cellulose esters containing long alkyl chain functional groups can be selected from the group consisting of cellulose acetate hexanoate, cellulose acetate nonanoate, cellulose acetate raurate, cellulose palmitate, cellulose acetate stearate, cellulose nonanoate, cellulose hexanoate, cellulose hexanoate propionate, and cellulose nonanoate propionate.

[0055] In some embodiments, the cellulose ester is a cellulose acetate propionate (CAP) having a propionyl content of greater than 49% (propionic acid content of greater than 66%) based on the total weight of the CAP polymer. In some embodiments, the cellulose ester is a cellulose acetate propionate (CAP) having a propionyl content of less than 38% (propionic acid content of less than 50%) based on the total weight of the CAP polymer.

[0056] In some embodiments, the cellulose ester is from 15% to 52%, or from 15% to 45%, or from 15% to 38%, or from 15% to 35%, or from 15% to 30%, or from 15% to 25%, or from 20% to 52%, or from 20% to 45%, or from 20% to 38%, or from 20% to 35%, or from 20% to 30%, or from 25% to 52%, or from 25% to 45%, or from 25% and cellulose acetate propionate (CAP) having a propionyl content in the range of 25% to 35%, 30% to 52%, 30% to 45%, 30% to 38%, 35% to 52%, 35% to 45%, 35% to 38%, 38% to 49%, or 49% to 52%.

[0057] In some embodiments, the cellulose ester is cellulose acetate butyrate (CAB) having a butyryl content of greater than 40% (butyric acid content of greater than 50%) based on the total weight of the CAB polymer. In some embodiments, the cellulose ester is cellulose acetate butyrate (CAB) having a butyryl content of less than 32% (butyric acid content of less than 40%) based on the total weight of the CAB polymer.

[0058] In some embodiments, the cellulose ester is present in an amount, as a percentage of the total weight of the polymer, of from 10% to 57%, or from 10% to 50%, or from 10% to 45%, or from 10% to 40%, or from 10% to 32%, or from 10% to 25%, or from 10% to 18%, or from 15% to 57%, or from 15% to 50%, or from 15% to 45%, or from 15% to 40%, or from 15% to 32%, or from 15% to 25%, or from 15% to 18%, or from 20% to 57%, or from 20% to 50%, or from 20% to 45%, or from 20% to 45%. and cellulose acetate butyrate (CAB) having a butyryl content in the range of 0%, or 20% to 32%, or 20% to 25%, or 25% to 57%, or 25% to 50%, or 25% to 45%, or 25% to 40%, or 25% to 32%, or 30% to 57%, or 30% to 50%, or 30% to 45%, or 35% to 57%, or 35% to 50%, or 35% to 40%, or 40% to 57%, or 40% to 50%, or 40% to 45%, or 45% to 57%, or 45% to 50%.

[0059] In some embodiments, the cellulose ester is present in an amount, as a percentage of the total weight of the polymer, of from 15% to 55%, or from 15% to 50%, or from 15% to 45%, or from 15% to 40%, or from 15% to 35%, or from 15% to 30%, or from 15% to 25%, or from 15% to 20%, or from 20% to 55%, or from 20% to 50%, or from 20% to 45%, or from 20% to 40%, or from 20% to 35%, or from 20% to 30%, or from 20% to 25%, or from 25% to 55%, or from 25% to 50%, or from 25% to 45%, or from 25% to 40%, or from 25% to 35%, or from 25% to 30%. or 30% to 55%, or 30% to 50%, or 30% to 45%, or 30% to 40%, or 30% to 35%, or 35% to 55%, or 35% to 50%, or 35% to 45%, or 35% to 40%, or 40% to 55%, or 40% to 50%, or 40% to 45%, or 40% to 55%, or 40% to 55%, or 40% to 55%, or 40% to 55%, or 40% to 45%, or 45% to 55%, or 45% to 50%, or 50% to 55%.

[0060] In some embodiments of the present invention, the EVA polymer may be any ethylene vinyl acetate rubber material compatible with the cellulose ester composition. By "compatible" we mean that the EVA polymer is of a type that provides a clear, non-cloudy cellulose ester composition with good clarity, with a Tg that is maintained compared to the base cellulose ester (without EVA), and with significantly increased toughness, preferably with an Izod impact strength at 23°C of at least 100 J / m. In some embodiments, the EVA polymer may be a single compatible polymer grade, a blend of different EVA compatible polymer grades, a combination of a compatible EVA polymer and a non-compatible EVA polymer (e.g., when a "non-compatible" EVA polymer is used as is in the same formulation), or a combination of a compatible EVA polymer and other impact modifiers, provided that the resulting cellulose ester composition has sufficient clarity and toughness. In some embodiments, the EVA is not modified with maleic anhydride. In one embodiment, the EVA is not modified (e.g., functionalized or reacted) with any other chemical substituents. EVA contains vinyl acetate. It is not considered to be modified by adjusting amounts (with other chemical substituents).

[0061] In some embodiments, ethylene / vinyl acetate (EVA) copolymers can be produced by known high and medium pressure processes, optionally in a solvent such as t-butanol. In some embodiments, the EVA copolymer has a vinyl acetate content of 30-98% by weight. In some embodiments of the present invention, the compatible EVA copolymer has a vinyl acetate content ranging from 40% to less than 80% by weight, or ranging from 40-70% by weight, preferably ranging from 50-65% by weight, or from greater than 50% to 65% by weight. In one embodiment, the cellulose ester composition comprises at least one compatible EVA copolymer having a vinyl acetate (VA) composition ranging from 40-70% by weight, preferably ranging from 50-65% by weight, or from greater than 50% to 65% by weight. In some embodiments, the amount of such compatible EVA copolymer (having a VA content of 40-70 wt%, preferably 50-65 wt%, or greater than 50 wt% to 65 wt%) in the cellulose ester composition is 0.5-40 wt%, or 1-35 wt%, or 2.5-30 wt%, or 5-30 wt%, or 10-30 wt%, or greater than 10 wt% to 30 wt%, or 12-25 wt%, or 15-30 wt%, or 15-25 wt%, or 15-20 wt%, based on the total cellulose ester composition.

[0062] In one embodiment of the invention, multiple EVA copolymers having different vinyl acetate contents can be used, so long as the weight average vinyl acetate content of the EVA blend is in the range of 40% to less than 80% by weight, or 40-70% by weight, preferably 50-65% by weight, or greater than 50% to 65% by weight. In some embodiments, the total amount of this mixture of compatible EVA copolymers (having a weight average VA content in the range of 40-70 wt%, preferably 50-65 wt%, or from greater than 50 wt% to 65 wt%) in the cellulose ester composition is 0.5-40 wt%, or 1-35 wt%, or 2.5-30 wt%, or 5-30 wt%, or 10-30 wt%, or from greater than 10 wt% to 30 wt%, or 12-25 wt%, or 15-30 wt%, or 15-25 wt%, or 15-20 wt%, based on the total cellulose ester composition. In some embodiments, the EVA (or EVA blend) has a VA content (or weight average VA content) in the range of 50-65 wt%, or from greater than 50 wt% to 65 wt%, or 51-65 wt%, or 52-65 wt%, or 53-65 wt%, or 51-64 wt%, or 51-62 wt%, or 51-60 wt%, or 52-64 wt%, or 52-62 wt%, or 52-60 wt%, or 53-64 wt%, or 53-62 wt%, or 53-60 wt%, based on the weight of the EVA component.

[0063] In some embodiments, the ethylene / vinyl acetate copolymers produced by the high pressure process have a melt index value (measured according to DIN 53,735 at 190° C. under a load of 2.16 kp) of 0.1 to 100 g, preferably 1.0 to 10 g, more preferably 4.5 to 6 g. The intrinsic viscosity measured in tetralin at 120° C. is generally 0.6 to 1.5 dL / g. The absolute molecular weight determined by light scattering is preferably 50,000 to about 1 million. The relationship M w / M nThe inconsistency factor (U), defined according to 1.-1 (G. Shulz, Z., Phys. Chem. (B) 43 (1939), p. 25-34), is between 1.6 and 30. These copolymers are preferably soluble in hydrocarbons at high temperatures.

[0064]

[0061] Ethylene / vinyl acetate copolymers, produced for example by solution or emulsion polymerization and containing 30-98% by weight, preferably 0-70% by weight, of vinyl acetate, have melt index values ​​(190°C / 2.16 kp) which may exceed 100 g, but the melt index is preferably in the range of less than 15 g, more particularly 0.5-5 g. The absolute molecular weight, measured by light scattering, is preferably in the range of 40,000-1,000,000. The disparity coefficient (U) is 1 to 6. The copolymer is soluble in hydrocarbons and alcohols, and preferably has an intrinsic viscosity in toluene of 0.5 to 2.5 dL / g.

[0065] In one embodiment, one or more impact modifiers can be included with the compatible EVA copolymer, and in some embodiments, the impact modifier can be any polymeric material classified as an elastomer having a glass transition temperature (Tg) below room temperature. Tg can be measured, for example, according to ASTM-D3418 using a TA2100 thermal analyzer with a scan rate of 20°C / min. Several classes of impact modifiers fit this description.

[0066] In one embodiment, the impact modifier can be selected from a class of materials known as modified polyolefins (or olefin copolymers) other than the EVA component (discussed herein). In this class, the olefin is copolymerized with an additional monomer that limits the crystallization of the polymer, increasing the amount of chains with a Tg below room temperature and decreasing the modulus below 500 MPa. Examples of modified olefins include EMA (examples include Elvaloy 4051, Lotader 3410, and Lotader 8900), EBA, EEA, EPDM (examples include Royaltuf 498), and EPR.

[0067] In one embodiment, the impact modifier may be a block copolymer in which at least one segment of the chain has a Tg below room temperature (called the soft segment) and at least one segment of the chain has a Tg or Tm above room temperature (called the hard segment). These block copolymers are also commonly referred to as thermoplastic elastomers (TPEs). Examples of block copolymers in this class include styrenic materials such as SBS, SEBS, and SIS (examples include Kraton G1657MS, Kraton FG1901G, and Kraton FG1924G); thermoplastic urethanes (TPUs) (examples include Elastolan 1170Z, Estane 2355, Estane ALR-CL87A, and Estane ALR-72A); polyester-ether copolymers (examples include Ecdel 9966 and Hytrel 3078). , or polyamide-ether copolymers (examples include Pebax 5533).

[0068] In one embodiment, the impact modifier can be selected from the class of emulsion-forming materials known as core-shell impact modifiers. In one embodiment, the impact modifier is an MBS core-shell impact modifier, such as methacrylate-butadiene-styrene, having a core formed from a butadiene-styrene copolymer and a shell formed from a methyl methacrylate-styrene copolymer. In another embodiment, the impact modifier is an acrylic core-shell impact modifier, having a core formed from an acrylic polymer, such as butyl acrylate or styrene butyl acrylate, and a shell formed from polymethyl methacrylate or a styrene methyl methacrylate copolymer.

[0069] In some embodiments, the MBS impact modifier may comprise a graft polymer composition comprising 10 to 70 weight percent of a polymer or copolymer of butadiene and a graft of a first methyl (meth)acrylate and a crosslinker, a second styrene, and a third graft of methyl (meth)acrylate and optionally a crosslinker.

[0070] Suitable monomers for polymerizing with conjugated diolefins, preferably butadiene, include alkenyl aromatic compounds, preferably vinyl aromatic compounds, such as styrene, divinylbenzene, α-methylstyrene, vinyltoluene, hydrogenated styrene; lower (CZ-Cu) alkyl acrylates, such as ethyl acrylate, n-propyl acrylate, n-butyl acrylate, Z-methylbutyl acrylate, 3-methylbutyl acrylate. , amyl acrylate, n-hexyl acrylate, Z-ethylhexyl acrylate; lower (C2-C 12 ) alkyl (meth)acrylates; acrylonitrile; olefins, and the like; or combinations of any of the above.

[0071]

[0068] Suitable crosslinking agents include divinylbenzene; di(meth)acrylates; diacrylates, such as mono-, di-, or diacrylates of polyethylene glycols; their (meth)acrylates; divinyl sulfide; divinyl ethers; vinyl acrylate; vinyl (meth)acrylate; trivinylbenzene; trimethylolpropane; tri(meth)acrylate; triallyl cyanurate and triallyl isocyanurate.

[0072] In one embodiment, the MBS core-shell impact modifier may comprise a copolymer of butadiene and styrene, most preferably a terpolymer of butadiene, styrene, and divinylbenzene. The relative amounts of the monomers making up the copolymer substrate may vary, but the butadiene component will usually comprise from about 30 to 100 parts by weight, the styrene component will comprise from 0 to about 70 parts by weight, and the divinylbenzene component will comprise from 0 to about 5 parts by weight, based on 100 parts by weight of the total of butadiene, styrene, and divinylbenzene. In one embodiment, the copolymer substrate may comprise from about 50 to about 90 parts by weight of butadiene, from about 10 to about 50 parts by weight of styrene, and from 0 to about 5 parts by weight of divinylbenzene, on the same basis, most preferably from about 65 to about 85 parts by weight of butadiene, from about 15 to about 35 parts by weight of styrene, and from about 0.5 to about 2.0 parts by weight of divinylbenzene, on the same basis.

[0073]

[0070] Examples of methacrylate-butadiene-styrene core-shell polymers include, but are not limited to, those described in patents US-4,446,585, US-5,534,594, and US-6,331,580. MBS core-shell impact modifiers are available from Kaneka as Kane Ace B564, from Arkema as Clearstrength, from Mitsubishi Chemical as Metablen C and Metablen E, from Dow as Paraloid, and from Evonik as Visiomer.

[0074]

[0071] In one embodiment of the present invention, the core-shell impact modifier is an acrylic impact modifier comprising about 25-95% by weight of a first elastomeric phase polymerized from a monomer system comprising about 75-99.8% by weight of a (C1-C6) alkyl acrylate, 0.1-5% by weight of a crosslinking monomer, and 0.1-5% by weight of a graft linking monomer, and about 75-5% by weight of a final rigid thermoplastic phase containing no epoxy groups polymerized in the presence of such elastomeric phase.

[0075]

[0072] Examples of useful acrylates are methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, etc. In some embodiments, the acrylates are n-butyl acrylate and ethyl acrylate.

[0076]

[0073] Graft link monomers are defined as polyethylenically unsaturated monomers having both a high reactivity double bond and a low reactivity double bond, the high reactivity double bond having a tendency to polymerize during the polymerization of the first stage monomers, leaving a residual double bond for polymerization during the next stage polymerization, thereby grafting the second stage polymer onto the first stage polymer. In some embodiments, the graft link monomers are allyl methacrylate, allyl acrylate, and diallyl maleate. In one embodiment, 0.05-3% of the graft link monomer is present based on the first stage monomer system. A crosslinking monomer is also preferably present, generally in an amount of about 0.05-3% by weight based on the first stage monomer system, which is defined as a polyethylenically unsaturated monomer having at least two double bonds of approximately equal reactivity to cause crosslinking in the first stage polymerization. Representative examples of crosslinking monomers include 1,3-butylene diacrylate, 1,3-butylene dimethacrylate, and divinylbenzene.

[0077] "Epoxy functionality" means epoxy units pendant from the final stage polymer. In some embodiments, epoxy functionality is introduced into the final stage polymer by using epoxy-containing monomers such as glycidyl acrylate or glycidyl methacrylate in the final stage monomer mix.

[0078]

[0075] Examples of acrylic core-shell polymers include, but are not limited to, those described in patents US-3,448,173, US-3,655,825, and US-3,853,968. Examples of suitable acrylic impact modifiers are Kane Ace ECO100 from Kaneka, Durastrength from Arkema, Elvaloy and Elvaloy HP from DuPont, Metablen W from Mitsubishi Chemical, and Paraloid from Dow.

[0079] In one class of this embodiment, the impact modifier is an ABS core-shell impact modifier having a core formed from a butadiene-styrene copolymer and a shell formed from an acrylonitrile-styrene copolymer. Examples of ABS core-shell impact modifiers include Blendex from Galata Chemicals and Elix from Elix Polymers.

[0080] In one class of this embodiment, the impact modifier is a silicone-acrylic core-shell impact modifier having a core formed from a silicone-acrylic rubber and a shell formed from a PMMA copolymer or a methyl methacrylate-styrene copolymer. An example of a silicone-acrylic core-shell impact modifier is Metablen S from Mitsubishi Chemical Company.

[0081] In one embodiment, the impact modifier has neutral acidity, which is believed to help prevent degradation of the cellulose ester during melt processing of the composition. In one embodiment, the impact modifier can be either a non-reactive impact modifier or a reactive impact modifier, or a combination of both. The impact modifier used can also improve the mechanical and physical properties of the cellulose ester composition.

[0082] In one embodiment, when a non-reactive impact modifier is used, the impact modifier comprises a first polymer chain segment that is more chemically or physically compatible with the cellulose ester than other polymer chain segments. In one embodiment, the first segment comprises a polar functional group that confers compatibility with the cellulose ester, such as, but not limited to, polar functional groups such as ethers, esters, amides, alcohols, amines, ketones, and acetals. Compatibility is defined by the preferential interaction of the first polymer chain segment with the cellulose ester polymer relative to the second segment, which may refer to molecular-scale or micro-scale interactions. The first segment may be comprised of oligomers or polymers of the following: cellulose esters, cellulose ethers, polyoxyalkylenes such as polyoxyethylene, polyoxypropylene, polyoxybutylene, polyglycols such as polyethylene glycol, polypropylene glycol, polybutylene glycol, polyesters such as polycaprolactone, polylactic acid, aliphatic polyesters, aliphatic-aromatic copolyesters, polyacrylates and polymethacrylates, polyacetals, polyvinylpyrrolidone, polyethylene vinyl acetate, polyvinyl acetate, and polyvinyl alcohol. In one embodiment, the first segment is polyethylene vinyl acetate, polyoxyethylene, or polyvinyl alcohol.

[0083] In some embodiments, the second segment may be either a saturated or unsaturated hydrocarbon group, or may contain both saturated and unsaturated hydrocarbon groups. The second segment may be an oligomer or a polymer. In one embodiment of the invention, the second segment of the non-reactive impact modifier is selected from the group consisting of polyolefins, polydienes, aromatic polymers, and copolymers. An example of an aromatic polymer second segment is polystyrene. An example of a copolymer second segment is a styrene / butadiene copolymer.

[0084]

[0082] The first and second segments of the non-reactive impact modifier may be diblock, triblock, branched, or comb-type structures. The weight average molecular weight (Mw) of the non-reactive impact modifier may range from about 300 to about 20,000, or from about 500 to about 10,000, or from about 1,000 to about 5,000. The segment ratio of the non-reactive impact modifier may range from about 15 to about 85% polar first segment / about 15 to about 85% non-polar second segment.

[0085]

[0083] Examples of non-reactive impact modifiers include, but are not limited to, ethoxylated alcohols, ethoxylated alkylphenols, ethoxylated fatty acids, polyethylene vinyl acetate, block polymers of propylene oxide and ethylene oxide, ethylene / propylene terpolymers, functionalized polyolefins, polyglycerol esters, polysaccharide esters, and sorbitan esters. Examples of ethoxylated alcohols are C 11 ~C 15 Secondary alcohol ethoxylates, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, and C ethoxylated with ethylene oxide 12 ~C 14 It is a natural linear alcohol. 11 ~C 15 The secondary alcohol ethoxylate is available from Dow Chemical Company as Dow Tergitol® 15S. Polyoxyethylene cetyl ether and polyoxyethylene stearyl ether are available from ICI Surfactants in their Brij® series of products. C ethoxylated with oxide 12 ~C 14 Natural linear alcohols are available from Hoechst Celanese in their Genapol® series of products. Examples of alkylphenols include octylphenoxypoly(ethyleneoxy)ethanol and nonylphenoxypoly(ethyleneoxy)ethanol. Octylphenoxypoly(ethyleneoxy)ethanol is available from Rhodia as the Igepal® CA series of products, and nonylphenoxypoly(ethyleneoxy)ethanol is available from Rhodia as the Igepal® CO series of products or from Dow Chemical Company as Tergitol® NP. Ethoxylated fatty acids include Henkel Polyethylene glycol monostearates or monolaurates available from Stepan under the Nopalcol® series of products; propylene oxide and ethylene oxide block polymers available from BASF under the Pluronic® series of products; polyglycerol esters available from Stepan under the Drewpol® series of products; Polysaccharide esters are available from Henkel in the Glucopon® series of products, which are alkyl polyglucosides. Sorbitan esters are available from ICI in the Tween® series of products.

[0086] In another embodiment of the present invention, the non-reactive impact modifier is synthesized in situ in the cellulose ester composition by reacting a compound compatible with the cellulose ester. These compounds may be, for example, telechelic oligomers, which are defined as prepolymers capable of initiating further polymerization or other reactions by virtue of their reactive end groups. In one embodiment of the invention, these in situ impact modifiers are , and may have a higher weight average molecular weight (Mw) of about 10,000 to about 1,000,000.

[0087] In another embodiment of the present invention, the impact modifier may be reactive. A reactive impact modifier may include a polymer or oligomer that is compatible with one component of the composition and a functional group that can react with the other component of the composition. In some embodiments, there are two types of reactive impact modifiers that can be used. The first reactive impact modifier has a hydrocarbon chain that is compatible with the cellulose ester and also has a functional group that can react with the cellulose ester. Such functional groups include, but are not limited to, carboxylic acid, anhydride, acid chloride, epoxide, and isocyanate. Specific examples of this type of reactive impact modifier include, but are not limited to, long chain fatty acids such as stearic acid (octadecanoic acid); long chain fatty acid chlorides such as stearoyl chloride (octadecanoyl chloride); long chain fatty acid anhydrides such as stearic anhydride (octadecanoic anhydride); epoxidized fatty esters; styrene maleic anhydride copolymers; maleic anhydride grafted polypropylene; copolymers of maleic anhydride with olefins and / or acrylic esters, such as terpolymers of ethylene, acrylic esters, and maleic anhydride; and copolymers of glycidyl methacrylate with olefins and / or acrylic esters, such as terpolymers of ethylene, acrylic esters, and glycidyl methacrylate.

[0088]

[0086] Reactive impact modifiers include SMA® 3000 styrene maleic anhydride copolymer from Sartomer / Cray Valley, Eastman G-3015® maleic anhydride grafted polypropylene from Eastman Chemical Company, Epolene® E-43 maleic anhydride grafted polypropylene from Westlake Chemical, Lotader® MAH 8200 random copolymer of ethylene, acrylic ester, and maleic anhydride from Arkema. terpolymer, Lotader® GMA AX8900 random terpolymer of ethylene, acrylic ester, and glycidyl methacrylate; and Lotarder® GMA AX8840 random terpolymer of glycidyl methacrylate.

[0089]

[0087] Reactive polyolefin impact modifiers are available as Lotader, Fusabond, Elvloy PTW, Lotryl, Elvaloy AC, InterLoy. The second type of reactive impact modifier has a polar chain compatible with cellulose esters and also has a functional group capable of reacting with cellulose esters. Examples of these types of reactive impact modifiers include cellulose esters or polyethylene glycols with olefin or thiol functional groups. Reactive polyethylene glycol impact modifiers with olefin functional groups include, but are not limited to, polyethylene glycol allyl ether and polyethylene glycol acrylate. Examples of reactive polyethylene glycol impact modifiers with thiol functional groups include polyethylene glycol thiols. Examples of reactive cellulose ester impact modifiers include mercaptoacetate cellulose esters.

[0090] In some embodiments of the present invention, the amount of impact modifier in the cellulose ester composition may range from about 1% to about 15% by weight, or from about 5% to about 10% by weight, based on the weight of the cellulose ester composition. In some embodiments, the cellulose ester composition comprises 55-98% by weight of at least one cellulose ester, preferably CAP; 1-30% by weight of at least one EVA copolymer, preferably EVA having a VA content of 40-70% by weight, preferably 50-65% by weight, or from 50% to 65% by weight, or a blend of EVAs (with different VA contents), the blend having an average VA content of 45-65% by weight, or 50-65% by weight, or from 50% to 65% by weight; and 1-15% by weight of at least one impact modifier, preferably a core-shell impact modifier.

[0091] In one embodiment, the cellulose ester and EVA copolymer composition is transparent and has a light transmittance of at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, as measured using a 3.2 mm plaque after injection molding according to ASTM-D1003 at a barrel set point of 249° C. and a 5 minute residence time. In some embodiments, the polymer base resin has a transmittance in the range of 70% to 95%, or 75% to 95%, or 80% to 95%, or 85% to 95%, or 90% to 95%, or 70% to 90%, or 75% to 90%, or 80% to 90%, or 85% to 90%, as measured using a 3.2 mm plaque after injection molding according to ASTM-D1003 at a barrel set point of 249° C. and a 5 minute residence time. In one class of this embodiment, the cellulose ester compositions comprising an EVA copolymer have a % haze of less than 10%. In some embodiments, the cellulose ester compositions comprising an EVA copolymer have a % haze of less than 8%, or less than 6%, or less than 5%.

[0092] In another embodiment, the refractive index (RI) of the EVA copolymer is sufficiently close to that of the cellulose ester to provide a composition with high transmission and low haze. In one embodiment, the EVA copolymer has an RI close to that of the cellulose ester, between about 1.46 and 1.48, providing a transparent composition. In some embodiments, the EVA copolymer and cellulose ester components have a refractive index difference: RI (second component) - RI (first component) (e.g., RI of CE - RI of EVA) of between about 0.006 and about -0.0006, and the blend has a transmission of at least 75% and a haze of 10% or less, more preferably 5% or less.

[0093] In some embodiments of the present invention, the amount of EVA copolymer in the cellulose ester composition may range from about 0.5% to about 40% by weight, or from about 1% to about 35% by weight, or from about 2.5% to about 30% by weight, or from about 5% to about 25% by weight, or from about 5% to about 20% by weight, or from about 5% to about 15% by weight, or from about 5% to about 10% by weight, or from about 10% to about 30% by weight, or from about 10% to about 25% by weight, or from about 10% to about 20% by weight, or from about 10% to about 15% by weight, or from about 10% to about 30% by weight, or from greater than 10% to about 25% by weight, or from greater than 10% to about 20% by weight, or from greater than 10% to about 15% by weight, based on the weight of the cellulose ester composition.

[0094]

[0093] In another embodiment of the present invention, the cellulose ester composition further comprises at least one additional polymer component as a blend (with the cellulose ester) in an amount of 5-95% by weight based on the total cellulose ester composition. Suitable examples of the additional polymer component include, but are not limited to, nylon; polyester; polyamide; polystyrene; other cellulose esters, cellulose ethers; polystyrene copolymers; styrene acrylonitrile copolymers; polyolefins; polyurethanes; acrylonitrile butadiene styrene copolymers; poly(methyl methacrylate); acrylic copolymers; poly(ether-imides); polyphenylene oxides; polyvinyl chloride; polyphenylene sulfides; polyphenylene sulfides / sulfones; poly(ester-carbonates); polycarbonates; polysulfones; polylactic acid; polybutylene succinates; polysulfone ethers; and poly(ether-ketones) of aromatic dihydroxy compounds; or mixtures of any of the above polymers. The blends can be formed by conventional processing techniques known in the art, such as melt blending or solution blending. In some embodiments, the total amount of additional polymeric components (not including EVA) is less than 25 wt%, or less than 20 wt%, or less than 15 wt%, or less than 10 wt%, or less than 5 wt%, or zero, based on the total weight of the cellulose ester composition.

[0095] In one embodiment of the present invention, in addition to the EVA copolymer, the composition may include a plasticizer. In some embodiments, the plasticizer used in the present invention may be any known in the art capable of lowering the glass transition temperature and / or melt viscosity of the cellulose ester to improve melt processing properties. The plasticizer may be any suitable plasticizer for use with cellulose esters. The level of plasticizer should be lower than the standard (or normal) plasticizer levels used in conventional / commercial cellulose esters; such that the composition has a higher Tg, better toughness, and better flow than a fully plasticized cellulose ester composition. In some embodiments, the plasticizer is present in an amount that does not substantially decrease the Tg of the cellulose ester composition compared to a similar composition without the plasticizer. In some embodiments, the Tg does not change (e.g., decrease) by more than 20%, or more than 15%, or more than 10%, or more than 5%, or more than 2% as a result of the inclusion of the plasticizer.

[0096]

[0095] The plasticizer may be either of monomeric or polymeric structure. In one embodiment, the plasticizer is at least one selected from the group consisting of aromatic phosphate ester plasticizers, alkyl phosphate ester plasticizers, dialkyl ether diester plasticizers, tricarboxylate ester plasticizers, polymeric polyester plasticizers, polyglycol diester plasticizers, polyester resin plasticizers, aromatic diester plasticizers, aromatic triester plasticizers, aliphatic diester plasticizers, carbonate plasticizers, epoxidized ester plasticizers, epoxidized oil plasticizers, benzoate plasticizers, polyol benzoate plasticizers, adipate plasticizers, phthalate plasticizers, glycolate ester plasticizers, citrate ester plasticizers, hydroxyl functional plasticizers, or solid amorphous resin plasticizers.

[0097] In one aspect of the invention, the plasticizer may be selected from at least one of the following: triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, diphenyl biphenyl phosphate, trioctyl phosphate, tributyl phosphate, diethyl phthalate, dimethoxyethyl phthalate, dimethyl phthalate, dioctyl phthalate, dibutyl phthalate, di-2-ethylhexyl phthalate, butyl benzyl phthalate, dibenzyl phthalate, butyl phthalyl butyl glycolate, ethyl phthalyl ethyl glycolate, methyl phthalyl ethyl glycolate, triethyl citrate, tri-n-butyl citrate, acetyl triethyl citrate, acetyl-tri-n-butyl citrate, and acetyl-tri-n-(2-ethylhexyl) citrate, diethylene glycol dibenzoate, dipropylene glycol dibenzoate, or triethylene glycol dibenzoate.

[0098] In another aspect of the invention, the plasticizer may be selected from at least one of the following: (i) an acid residue including one or more residues of phthalic acid, adipic acid, trimellitic acid, succinic acid, benzoic acid, azelaic acid, terephthalic acid, isophthalic acid, butyric acid, glutaric acid, citric acid, or phosphoric acid; and (ii) an alcohol residue including one or more residues of an aliphatic, alicyclic, or aromatic alcohol containing about 20 or fewer carbon atoms.

[0099] In another aspect of the invention, the plasticizer may be selected from at least one of the following: (i) at least one acid residue selected from the group consisting of phthalic acid, adipic acid, trimellitic acid, succinic acid, benzoic acid, azelaic acid, terephthalic acid, isophthalic acid, butyric acid, glutaric acid, citric acid, or phosphoric acid; and (ii) at least one alcohol residue selected from the group consisting of aliphatic, alicyclic, or aromatic alcohols containing about 20 or less carbon atoms.

[0100] In another embodiment of the present invention, the plasticizer may contain an alcohol residue, which may be one of the following: stearyl alcohol, lauryl alcohol, phenol, phenyl alcohol ... At least one selected from benzyl alcohol, hydroquinone, catechol, resorcinol, ethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, and diethylene glycol.

[0101] In another embodiment of the invention, the plasticizer is one of the following: benzoate, phthalate, In another embodiment, the plasticizer comprises diethylene glycol dibenzoate (abbreviated herein as "DEGDB").

[0102] In another embodiment of the present invention, the plasticizer is one of the following: 10 Diacid residues, For example, residues of malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid; and C2-C 10 The polyester may be selected from at least one aliphatic polyester containing diol residues.

[0103] In another embodiment, the plasticizer is selected from the group consisting of the following C2 to C 10 Diol: Ethylene glycol The diol residue may be at least one residue of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,5-pentylene glycol, triethylene glycol, and tetraethylene glycol.

[0104] In another embodiment of the present invention, the plasticizer may be, for example, polyethylene glycol. Examples of suitable polyglycols include polyglycols such as polypropylene glycol, polybutylene glycol, and polypropylene glycol. These may range from low molecular weight dimers and trimers to high molecular weight oligomers and polymers. In one embodiment, the weight average molecular weight (Mw) of the polyglycols may range from about 200 to about 2000.

[0105]

[0104] In another aspect of the invention, the plasticizer comprises at least one of the following: Resoflex® R296 plasticizer, Resoflex® 804 plasticizer, SHP (sorbitol hexapropionate), XPP (xylitol pentapropionate), XPA (xylitol pentaacetate), GPP (glucose pentaacetate), GPA (glucose pentapropionate), and APP (arabitol pentapropionate).

[0106]

[0105] In another embodiment of the present invention, the plasticizer is (A) about 5 to about 95% by weight of C2- C 12 (B) a carbohydrate organic ester (the carbohydrate contains from about 1 to about 3 monosaccharide units); and (B) from about 5 to about 95% by weight of a C2-C 12 Polyol esters, wherein the polyol is derived from a C5 or C6 carbohydrate. In one embodiment, the polyol esters are free or do not contain one or more polyol acetates.

[0107] In another embodiment, the plasticizer comprises at least one carbohydrate ester; The carbohydrate portion of the carbohydrate ester is derived from one or more compounds selected from the group consisting of glucose, galactose, mannose, xylose, arabinose, lactose, fructose, sorbose, sucrose, cellobiose, cellotriose, and raffinose.

[0108] In another embodiment of the present invention, the plasticizer is at least one carbohydrate ester. wherein the carbohydrate portion of the carbohydrate ester comprises one or more of α-glucose pentaacetate, β-glucose pentaacetate, α-glucose pentapropionate, β-glucose pentapropionate, α-glucose pentabutyrate, and β-glucose pentabutyrate.

[0109] In another embodiment, the plasticizer comprises at least one carbohydrate ester; The carbohydrate portion of the carbohydrate ester may include an α-anomer, a β-anomer, or a mixture thereof.

[0110] In another embodiment, the plasticizer is: propylene glycol dibenzoate. In one embodiment, the benzoate may be selected from at least one of glyceryl tribenzoate, glyceryl tribenzoate, diethylene glycol dibenzoate, triethylene glycol dibenzoate, dipropylene glycol dibenzoate, and polyethylene glycol dibenzoate.

[0111]

[0110] In another embodiment of the present invention, the plasticizer may be a solid amorphous resin. These resins may contain some aromatic or polar functional groups, which can reduce the melt viscosity of cellulose ester.In one aspect of the present invention, the plasticizer can be a solid amorphous compound (resin), such as rosin; hydrogenated rosin; stabilized rosin and their monofunctional alcohol ester or polyol ester; modified rosin, such as (but not limited to) maleic acid and phenolic modified rosin and their ester; terpene resin; phenolic modified terpene resin; coumarin-indene resin; phenolic resin; alkylphenol-acetylene resin; and phenol-formaldehyde resin.

[0112] In another embodiment of the present invention, the plasticizer is triacetin, trimethylphosphene phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, triethyl citrate, acetyl trimethyl citrate, acetyl triethyl citrate, acetyl tributyl citrate, tributyl-o-acetyl citrate, dibutyl phthalate, diaryl phthalate, diethyl phthalate, dimethyl phthalate, di-2-methoxyethyl phthalate, dioctyl phthalate, dioctyl adipate, dibutyl tartrate, ethyl o-benzoyl benzoate, ethyl phthalyl ethyl glycolate, methyl phthalyl ethyl glycolate, n-ethyl toluenesulfonamide, o-cresyl p-tolylate benzene sulfonate, aromatic diol, substituted aromatic diol, aromatic ether, tripropionin, tribenzoin, polycaprolactone, glycerin, glycerin ester, diacetin, glycerol acetate benzoate, polyethylene glycol, polyethylene glycol ester, polyethylene glycol diester, di-2-ethylhexyl polyethylene glycol ester, triethylene glycol bis-2-ethylhexanoate, glycerol ester, diethylene glycol, polypropylene glycol, polyglycol diglycidyl ether, dimethyl sulfoxide, N-methylpyrrolidinone, C1-C 20Dicarboxylates, dimethyl adipate, dibutyl maleate, dioctyl maleate, resorcinol monoacetate, catechol, catechol esters, phenols, epoxidized soybean oil, castor oil, linseed oil, epoxidized linseed oil, other vegetable oils, other seed oils, polyethylene glycol-based bifunctional glycidyl ethers, gamma-valerolactone, alkyl phosphate esters, aryl phosphate esters, phospholipids, eugenol, cinnamyl alcohol, camphor, methoxyhydroxyacetophenone, vanillin, ethyl vanillin, 2-phenoxyethanol, glycol ethers, glycol esters, glycol ester ethers, polyglycol ethers, polyglycol esters, ethylene glycol ethers, propylene glycol ethers, ethylene glycol esters, propylene glycol esters, polypropylene glycol esters, acetylsalicylic acid, acetaminophen, naproxen, imidazole, triethanolamine, benzoic acid, benzyl benzoate, salicylic acid, 4-hydroxybenzoic acid, propyl-4-hydroxybenzoate, methyl-4-hydroxybenzoate, ethyl-4-hydroxybenzoate, benzyl-4-hydroxybenzoate, diethylene glycol dibenzoate, dipropylene glycol dibenzoate, triethylene glycol dibenzyl and at least one plasticizer selected from the group consisting of benzoates, butylated hydroxytoluene, butylated hydroxyanisole, sorbitol, xylitol, ethylenediamine, piperidine, piperazine, hexamethylenediamine, triazine, triazole, pyrrole, and any combination thereof.

[0113] The amount of plasticizer in the cellulose ester composition is determined by the amount of the plasticizer in the cellulose ester composition. The amount may range from 0 to about 15% by weight based on the weight of the composition. In one embodiment, the amount may be in the range of about 15% by weight or less based on the weight of the cellulose ester composition. In another embodiment, the amount may be in the range of about 10% by weight or less based on the weight of the cellulose ester composition. In another embodiment, the amount may be in the range of about 5% by weight or less based on the weight of the cellulose ester composition, or about 3% by weight or less based on the weight of the cellulose ester composition.

[0114] In other embodiments of the invention, the composition does not contain a plasticizer. In some embodiments, the composition does not include a polyetherester compound. In some embodiments, the composition does not include an adipic acid compound. In some embodiments, the cellulose ester composition includes 65 to 99 wt % of one or more cellulose esters, 1 to 35 wt % of one or more EVA copolymers, and less than 5 wt % in total of other components, based on the total weight of the cellulose ester composition. In some embodiments, such other components do not include a plasticizer, a polyetherester compound, or an adipic acid compound.

[0115] In another embodiment of the present invention, the composition is melt processable. Melt processability is characterized by: Generally, it refers to the ability of materials to be thermally processed below their decomposition temperature to obtain uniform pellets or plastic articles. For example, the compositions described are manufactured by Werner & Pflerderer It can be melt extruded at a throughput of 35 lbs / hr using a screw speed of 250 rpm and a barrel temperature of 240° C. in a 30 mm twin screw extruder, and / or injection molded using a barrel temperature of 240° C. and a mold temperature of 160° F. in a Toyo 110 injection molding machine with minimal molecular weight loss (e.g., less than 5% Mw loss from the original Mw) or discoloration (e.g., less than 5% haze increase or less than 5% transmittance decrease based on a 0-100% scale).

[0116]

[0115] In one embodiment of the present invention, 1 to 35 wt. % or 2.5 to 30 wt. % of EV Provided is a melt-processable cellulose ester composition that includes an A copolymer and does not include a plasticizer, and has a glass transition temperature (Tg) of at least 120°C (measured at 20°C / min as further described herein according to ASTM-D3418), and a notched Izod impact strength value of greater than 100 J / m (measured at 23°C on 3.2 mm thick bars according to ASTM-D256), and a spiral flow value of at least 38 centimeters (15 inches) measured at a barrel temperature of 240°C using the procedure described herein.Unless otherwise specified, notched Izod impact strength testing is performed at 23°C on molded bars after conditioning at 23°C and 50% RH for 48 hours on 3.2 mm thick bars, after notching.

[0117] The spiral flow was determined as follows: 110 ton clamping force and 32 mm A reciprocating screw injection molding machine having a screw diameter of 0.50" was fitted with a water-cooled cold runner mold having a spiral shaped cavity with dimensions of 0.50" wide x 0.030" deep x 60.00" long. The cavity was fed through a 3.5" long cold sprue having a 0.400" nominal diameter and a 3° taper, followed by a 1.0" long cold runner having a 0.30" nominal diameter, followed by a rectangular gate measuring 0.25" wide x 0.030" thick x 0.10" long. Regarding the scope of the experiment Variables controlled included resin drying, injection unit barrel temperature, mold temperature, initial injection rate, injection pressure limit, screw rotation speed, and back pressure on screw recovery, injection time, and cycle time. For each combination of variables, the response included actual melt temperature and distance traveled by the melt in the helical cavity (excluding runners and gates). The injection process was allowed to stabilize at each set of conditions (usually 10-15 shots) and then 10 molded specimens were collected with the average flow length reported. All materials were molded using pressure control with a mold temperature of 120°F, an initial injection rate of 1 inch / sec, an injection unit pressure limit of 2000 psi, a 5 second injection time, a 32 second cycle time, a 0.2 inch maximum cushion, a screw recovery rotation speed of 150 rpm, and a screw recovery back pressure of 100 psi.

[0118] In another embodiment of the present invention, the composition is prepared according to ASTM-D4440. Rheometrics were measured using frequency scans between 1 rad / s and 100 rad / s. It has a melt viscosity at 230° C. and 100 rad / sec of less than 10,000 P as measured by a plate-plate melt rheometer such as a Dynamic Analyzer (RDA II) using parallel plates of 25 mm diameter, a 1 mm gap, and 10% strain.

[0119] In one embodiment, an EVA copolymer or a mixture of EVA copolymers is Additionally, the melt processable cellulose ester composition comprises 0-15 wt% of an impact modifier, 0-15 wt% of a plasticizer, and has a Tg greater than 120°C. In another embodiment, the melt processable cellulose ester composition comprises 0-15 wt% of an impact modifier, 0-10 wt% of a plasticizer, and has a Tg greater than 130°C. In yet another embodiment, the melt processable cellulose ester composition comprises 0-10 wt% of an impact modifier, 0-10 wt% of a plasticizer, and has a Tg greater than 140°C. In another embodiment, the melt processable cellulose ester composition comprises 0-10 wt% of an impact modifier, 0-5 wt% of a plasticizer, and has a Tg greater than 140°C.

[0120] In another embodiment of the present invention, the cellulose ester composition comprises an EVA copolymer. The incorporation of one or more EVA copolymers and the absence of plasticizers results in a Tg comparable to that of the base cellulose ester polymer, with only a few degrees Celsius (e.g., less than 5° C., or less than 2° C.) drop. In some embodiments, the impact properties of these compositions also exceed 100 J / m (notched Izod impact strength at 23° C.).

[0121] In some embodiments of the present invention, the polymer-based resin is heated to a temperature above 100° C. Or greater than 110° C., or greater than 120° C. In some embodiments, the polymer base resin has a Tg of at least 120° C., or at least 125° C., or at least 130° C., or at least 135° C., or at least 140° C. In some embodiments, the polymer-based resin has a Tg in the range of 100°C to 150°C, 100°C to 145°C, 100°C to 140°C, 100°C to 135°C, 100°C to 130°C, 100°C to 125°C, 110°C to 150°C, 110°C to 145°C, 115°C to 150°C, 115°C to 145°C, 120°C to 150°C, 120°C to 145°C, 125°C to 150°C, 125°C to 145°C, 130°C to 150°C, 130°C to 145°C, 135°C to 150°C, 135°C to 145°C, 140°C to 150°C, 140°C to 145°C, or 145°C to 150°C.

[0122] In some embodiments of the present invention, the polymer base resin is a cellulose ester resin having a viscosity of 1000:1 or higher, preferably 1000:1 or higher, more preferably 1000:1 or higher. 56, measured on 3.2 mm thick bars subjected to 50% relative humidity at 23° C. for 48 hours, is at least 80 J / m, or at least 90 J / m, or at least 100 J / m, or at least 110 J / m, or at least 120 J / m, or at least 130 J / m, or at least 140 J / m, or at least 150 J / m, or In some embodiments, the polymer base resin has a notched Izod impact strength of from about 80 J / m to about 500 J / m, from about 80 J / m to about 400 J / m, from about 80 J / m to about 300 J / m, from about 80 J / m to about 200 J / m, from about 100 J / m to about 500 J / m, from about 80 J / m to about 300 J / m, from about 80 J / m to about 200 J / m, from about 100 J / m to about 500 J / m, from about 100 J / m to about 600 J / m, from about 100 J / m to about 700 J / m, from about 100 J / m to about 800 J / m, from about 100 J / m to about 900 J / m, from about 100 J / m to about 1500 J / m, from about 150 J / m to about 160 J / m, from about 170 J / m to about 180 J / m, from about 190 J / m to about 200 J / m, from about 200 J / m to about 300 J / m, from about 200 J / m to about 1500 J / m, from about 200 J / m to about 2500 J / m, from about 250 J / m to about 300 J / m, from about 20 ... m ~ about 500J / m, about 100J / m - about 400J / m, about 100J / m - about 300J / m, about 100J / m - about 200J / m, about 120J / m - about 500J / m, Approx. 120J / m~Approx. 400J / m, Approx. 120J / m~Approx. 300J / m, Approx. 120J / m~Approx. 200J / m, Approx. 150J / m~Approx. 500J / m, Approx. 150J / m~Approx. 40 0J / m, about 150J / m to about 300J / m, about 150J / m to about 200J / m, about 170J / m to about 500J / m, about 170J / m to about 400J / m, about 170J / m ~ approx. 300J / m, approx. 170J / m ~ approx. 200J / m, 180J / m ~ approx. 500J / m, approx. 180J / m ~ approx. 400J / m, approx. 180J / m ~ approx. 300J / m, approx. It has a notched Izod impact strength in the range of 180 J / m to about 200 J / m, 190 J / m to about 500 J / m, about 190 J / m to about 400 J / m, about 190 J / m to about 300 J / m, about 190 J / m to about 200 J / m, 200 J / m to about 500 J / m, about 200 J / m to about 400 J / m, or about 200 J / m to about 300 J / m.

[0123] In some embodiments, the polymer base resin is prepared according to ASTM-D256. Thus, it has a notched Izod impact strength, measured on 3.2 mm thick bars subjected to 48 hours at 23°C and 50% relative humidity, of at least 300 J / m, or at least 325 J / m, or at least 350 J / m, or at least 400 J / m, or at least 450 J / m, or at least 500 J / m. In some embodiments, when the notched Izod impact strength is at least 300 J / m, or at least 325 J / m, or at least 350 J / m, or at least 400 J / m, or at least 450 J / m, or at least 500 J / m, the Tg may be in the range of 80°C to 130°C, 80°C to 125°C, 80°C to 120°C, 85°C to 130°C, 85°C to 125°C, 90°C to 130°C, 90°C to 125°C, 95°C to 130°C, 95°C to 125°C, 100°C to 130°C, 100°C to 125°C, 105°C to 130°C, 105°C to 125°C, 110°C to 130°C, 110°C to 125°C, or 110°C to 120°C.

[0124] In some embodiments of the present invention, a 3.2 mm thick polymer-based resin The plaques exhibit ductile failure as defined in Section 1.8 of ASTM-D3763 when tested by instrumented impact in accordance with ASTM-D3763.

[0125] In some embodiments of the present invention, the polymer base resin is 90, at 23° C. and 50% relative humidity for 48 hours, using 3.2 mm thick bars. In some embodiments, the polymer-based resin has a flexural modulus of at least 1900 MPa, at least 2000 MPa, at least 2100 MPa, at least 2200 MPa, at least 2300 MPa, or at least 2400 MPa, measured using 3.2 mm thick bars at 23° C. and 50% relative humidity for 48 hours, using ASTM-D790. In some embodiments, the polymer-based resin has a flexural modulus of about 1800 to about 3000 MPa, about 1900 to about 3000 MPa, about 2000 to about 3000 MPa, about 2100 to about 3000 MPa, about 2200 to about 3000 MPa, about 2300 to about 3000 MPa, about 2400 to about 3000 MPa, or about 2500 to about 3000 MPa, as measured using 3.2 mm thick bars subjected to 50% relative humidity at 23° C. for 48 hours in accordance with ASTM-D790. It has a flexural modulus of elasticity of about 1900 to about 2500 MPa, about 1900 to about 2800 MPa, or about 1900 to about 3000 MPa, as measured using a bar having a thickness of 3.2 mm.

[0126] In some embodiments of the present invention, the cellulose ester composition comprises a cellulose ester. The ester composition comprises 2.5% to 30% by weight of an EVA copolymer or a mixture of EVA copolymers, based on the total weight of the ester composition, and has a Tg value greater than 120°C, a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m, and a viscosity less than 10,000 P at 230°C and 100 rad / sec.

[0127] In some embodiments of the present invention, the cellulose ester composition comprises a cellulose ester. The ester composition comprises 2.5% to 30% by weight of an EVA copolymer or a blend of EVA copolymers, based on the total weight of the ester composition, and has a Tg value greater than 120°C, a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m, and a light transmission value greater than 80%, or at least 85%, or at least 90%, as measured using 3.2 mm plaques after injection molding according to ASTM-D1003 with a barrel set point of 249°C and a 5 minute residence time.

[0128]

[0127] Cellulose esters containing no or low levels of plasticizers were screened. One problem that can occur during melt processing in a screw plasticizing injection molding machine is that the screw may have difficulty recovering smoothly, resulting in poor material feeding and "squeaking" noises. Surprisingly, it has been found that by adding the EVA copolymer according to some embodiments of the present invention, these problems during injection molding can be eliminated.

[0129] In some embodiments of the present invention, the cellulose ester composition comprises a cellulose ester. The ester composition comprises 2.5% to 30% by weight of an EVA copolymer or a blend of EVA copolymers based on the total weight of the ester composition, has a Tg value greater than 120°C, a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m, and does not emit squealing noises or have screw recovery issues during injection molding at a barrel set point of 249°C.

[0130] In some embodiments of the present invention, the cellulose ester composition comprises a cellulose ester. % based on the total weight of the ester composition, and has a Tg value greater than 120°C, a notched Izod impact strength value greater than 150 J / m, and no squealing or screw recovery problems during injection molding at a barrel set point of 249°C.

[0131] In some embodiments of the present invention, the cellulose ester composition comprises a cellulose ester. The ester composition comprises 2.5% to 30% by weight of an EVA copolymer or a mixture of EVA copolymers, based on the total weight of the ester composition, and has a Tg value greater than 100°C, a notched Izod impact strength value greater than 200 J / m, and a viscosity less than 10,000 P at 230°C and 100 rad / sec.

[0132] In some embodiments of the present invention, the cellulose ester composition comprises a cellulose ester. % by weight based on the total weight of the ester composition, of an EVA copolymer or a mixture of EVA copolymers, and having a Tg value of greater than 120°C, a notched Izod impact strength value of greater than 200 J / m, and a thermal stability of greater than 249°C according to ASTM-D1003. and a 5 minute residence time, and have a light transmission value of greater than 80%, or at least 85%, or at least 90%, as measured using 3.2 mm plaques after injection molding at a barrel set point of 100 psi and a residence time of 5 minutes.

[0133] In some embodiments, the cellulose ester composition comprises a CAP resin, a cellulose % of an EVA copolymer or a mixture of EVA copolymers, and 5 to 15 weight % of a plasticizer, based on the total weight of the ester composition, and having a Tg value greater than 80° C., a notched Izod impact strength value greater than 500 J / m, or greater than 600 J / m, a viscosity less than 10,000 P at 230° C. and 100 rad / sec, and a light transmission value greater than 80%, or at least 85%, or at least 90%, as measured using 3.2 mm plaques after injection molding according to ASTM-D1003 at a barrel set point of 249° C. and a 5 minute residence time.

[0134] In some embodiments, the cellulose ester composition comprises a CAP resin, a cellulose and a plasticizer in the range of 5 to 15 weight percent, based on the total weight of the ester composition, and having a Tg value greater than 120° C., a notched Izod impact strength value greater than 350 J / m, or greater than 400 J / m, a viscosity less than 10,000 P at 230° C. and 100 rad / sec, and a light transmission value greater than 80%, or at least 85%, or at least 90%, as measured using 3.2 mm plaques after injection molding according to ASTM-D1003 at a barrel set point of 249° C. and a 5 minute residence time.

[0135] In some embodiments, the cellulose ester composition comprises a CAP resin, a cellulose and a Tg value greater than 140° C., a notched Izod impact strength value greater than 200 J / m, a viscosity less than 10,000 P at 230° C. and 100 rad / sec, and a light transmission value greater than 80%, or at least 85%, or at least 90%, as measured using 3.2 mm plaques after injection molding according to ASTM-D1003 at a barrel set point of 249° C. and a 5 minute residence time.

[0136] In some embodiments, the cellulose ester composition comprises a CAP resin, a cellulose and has a Tg value greater than 140° C., a notched Izod impact strength value greater than 250 J / m, or greater than 300 J / m, or greater than 400 J / m, a viscosity less than 10,000 P at 230° C. and 100 rad / sec, and a light transmission value greater than 80%, or at least 85%, or at least 90%, as measured using 3.2 mm plaques after injection molding according to ASTM-D1003 at a barrel set point of 249° C. and a 5 minute residence time.

[0137] In some embodiments, the cellulose ester composition comprises a CAB resin, a cellulose and a Tg value greater than 130° C., a notched Izod impact strength value greater than 250 J / m, a viscosity less than 10,000 P at 230° C. and 100 rad / sec, and a light transmission value greater than 80%, or at least 85%, or at least 90%, as measured using 3.2 mm plaques after injection molding according to ASTM-D1003 at a barrel set point of 249° C. and a 5 minute residence time.

[0138] In some embodiments of the present invention, the cellulose ester composition is applied to a thickness of 3.2 mm. The plaque of m comprises 2.5% to 30% by weight of an EVA copolymer or a mixture of EVA copolymers (having a VA content or weight average VA content of 50-65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, and the polymer base resin exhibits ductile fracture as defined in Section x1.8 of ASTM-D3763 when tested by instrumented impact in accordance with ASTM-D3763 and has a Tg value greater than 120°C.

[0139] In some embodiments of the present invention, the cellulose ester composition is applied to a thickness of 3.2 mm. The plaque of m comprises 2.5 wt% to 30 wt% EVA copolymer or a mixture of EVA copolymers (having a VA content or weight average VA content of 50-65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, and the polymer base resin exhibits ductile fracture as defined in Section X1.8 of ASTM-D3763 when tested by instrumented impact according to ASTM-D3763, has a Tg value greater than 120°C, a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m, and a viscosity of less than 10,000 P at 230°C and 100 rad / sec.

[0140] In some embodiments of the present invention, the cellulose ester composition is applied to a thickness of 3.2 mm. The plaque of 1.0 mm comprises 2.5 wt % to 30 wt % EVA copolymer or a mixture of EVA copolymers (having a VA content or weight average VA content of 50-65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, and the polymer base resin exhibits ductile failure as defined in Section 1.8 of ASTM-D3763 when tested by instrumented impact according to ASTM-D3763, has a Tg value greater than 120° C., a notched Izod impact strength value greater than 250 J / m, a viscosity less than 10,000 P at 230° C. and 100 rad / sec, and a light transmission value of greater than 80%, or at least 85%, or at least 90%, as measured using a 3.2 mm plaque after injection molding according to ASTM-D1003 at a barrel set point of 249° C. and a 5 minute residence time.

[0141] In some embodiments of the present invention, a 3.2 mm thick plaque of the CAP composition is comprises 2.5% to 30% by weight of an EVA copolymer or a mixture of EVA copolymers (having a VA content or weight average VA content of 50-65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, and the polymer base resin exhibits ductile fracture as defined in Section X1.8 of ASTM-D3763 when tested by instrumented impact in accordance with ASTM-D3763 and has a Tg value greater than 120°C.

[0142] In some embodiments of the present invention, a 3.2 mm thick plaque of the CAP composition is comprises 2.5% to 30% by weight of an EVA copolymer or a mixture of EVA copolymers (having a VA content or weight average VA content of 50 to 65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, the polymer-based resin exhibits ductile fracture as defined in Section X1.8 of ASTM-D3763 when tested by instrumented impact according to ASTM-D3763, has a Tg value greater than 120°C, a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m, and a viscosity of less than 10,000 P at 230°C and 100 rad / sec.

[0143] In some embodiments of the present invention, a 3.2 mm thick plaque of the CAP composition is is 2.5% by weight to 30% by weight of EVA based on the total weight of the cellulose ester composition. The polymer base resin includes a copolymer or blend of EVA copolymers (having a VA content or weight average VA content of 50-65%, or greater than 50% to 65%), exhibiting a ductile fracture as defined in Section X1.8 of ASTM-D3763 when tested by instrumented impact in accordance with ASTM-D3763, has a Tg value greater than 120°C, a notched Izod impact strength value greater than 250 J / m, a viscosity less than 10,000 P at 230°C and 100 rad / sec, and a light transmission value greater than 80%, or at least 85%, or at least 90%, as measured using 3.2 mm plaques after injection molding in accordance with ASTM-D1003 at a barrel set point of 249°C and a 5 minute residence time.

[0144] In some embodiments of the present invention, the cellulose ester composition is applied to a thickness of 3.2 mm. The plaque of m comprises a total of 2.5% to 30% by weight of two or more EVA copolymers (having a weight average VA content of 50-65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, and the polymer base resin exhibits ductile fracture as defined in Section x1.8 of ASTM-D3763 when tested by instrumented impact in accordance with ASTM-D3763 and has a Tg value greater than 120°C.

[0145] In some embodiments of the present invention, the cellulose ester composition is applied to a thickness of 3.2 mm. The plaque of m comprises a total of 2.5% to 30% by weight of two or more EVA copolymers (having a weight average VA content of 50 to 65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, and the polymer base resin exhibits ductile fracture as defined in Section X1.8 of ASTM-D3763 when tested by instrumented impact according to ASTM-D3763, has a Tg value greater than 120°C, a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m, and a viscosity of less than 10,000 P at 230°C and 100 rad / sec.

[0146] In some embodiments of the present invention, a 3.2 mm thick plate of cellulose ester is The Lark comprises a total of 2.5% to 30% by weight of two or more EVA copolymers (having a weight average VA content of 50 to 65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, the polymer base resin exhibiting ductile fracture as defined in Section x1.8 of ASTM-D3763 when tested by instrumented impact in accordance with ASTM-D3763, a Tg value greater than 120°C, a notched Izod impact strength value greater than 250 J / m, a viscosity less than 10,000 P at 230°C and 100 rad / sec, and a light transmittance value greater than 80%, or at least 85%, or at least 90%, measured using a 3.2 mm plaque after injection molding at a barrel set point of 249°C and a 5 minute residence time in accordance with ASTM-D1003.

[0147] In some embodiments of the present invention, a 3.2 mm thick plaque of the CAP composition is comprises a total of 2.5% to 30% by weight of two or more EVA copolymers (having a weight average VA content of 50-65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, and the polymer base resin exhibits ductile fracture as defined in Section X1.8 of ASTM-D3763 when tested by instrumented impact in accordance with ASTM-D3763 and has a Tg value greater than 120°C.

[0148] In some embodiments of the present invention, the CAP plaque is 3.2 mm thick. The cellulose ester composition comprises a total of 2.5% to 30% by weight of two or more EVA copolymers (having a weight average VA content of 50-65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, and the polymer base resin has a viscosity as specified in Section 1.8 of ASTM-D3763 when tested by instrumented impact in accordance with ASTM-D3763. C., have a Tg value greater than 120.degree. C., a notched Izod impact strength value greater than 100 J / m, or greater than 125 J / m, or greater than 150 J / m, and a viscosity less than 10,000 P at 230.degree. C. and 100 rad / sec.

[0149] In some embodiments of the present invention, the 3.2 mm thick plaque of the CAP is The polymer base resin comprises a total of 2.5% to 30% by weight of two or more EVA copolymers (having a weight average VA content of 50 to 65%, or greater than 50% to 65%) based on the total weight of the cellulose ester composition, and the polymer base resin exhibits a ductile fracture as defined in Section X1.8 of ASTM-D3763 when tested by instrumented impact in accordance with ASTM-D3763, a Tg value greater than 120°C, a notched Izod impact strength value greater than 250 J / m, a viscosity less than 10,000 P at 230°C and 100 rad / sec, and a light transmittance value greater than 80%, or at least 85%, or at least 90%, measured using a 3.2 mm plaque after injection molding in accordance with ASTM-D1003 at a barrel set point of 249°C and a 5 minute residence time.

[0150] In another embodiment of the present invention, the cellulose ester composition further comprises an antioxidant, a heat The composition may further comprise at least one additive selected from the group consisting of stabilizers, release agents, antistatic agents, brighteners, colorants, flow aids, processing aids, plasticizers, anti-fog additives, inorganics, UV stabilizers, lubricants, chain extenders, nucleating agents, reinforcing fillers, wood or wood flour fillers, glass fibers, carbon fibers, flame retardants, dyes, pigments, colorants, additional resins, and combinations thereof.

[0151] In some embodiments, in addition to EVA (discussed herein), a cellulose ester may be used. The cellulose ester composition includes a stabilizer selected from the group consisting of a secondary antioxidant, an acid scavenger, or a combination thereof. In some embodiments, in addition to EVA (discussed herein), the cellulose ester composition includes a secondary antioxidant in the range of about 0.1 to about 0.8 wt %, based on the total weight of the composition. In some embodiments, in addition to EVA (discussed herein), the cellulose ester composition includes an acid scavenger in the range of about 0.2 to about 2.0 wt %, based on the total weight of the composition. In one embodiment, in addition to EVA (discussed herein), the cellulose ester composition includes a secondary antioxidant in the range of about 0.1 to about 0.8 wt %, based on the total weight of the composition, and an acid scavenger in the range of about 0.2 to about 2.0 wt %. In one embodiment, the secondary antioxidant is 3,9-bis(2,4-di-tert-butylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane. In one embodiment, the acid scavenger is an epoxidized fatty acid ester. In one embodiment, the cellulose ester composition further comprises a salt stabilizer, for example in the range of about 0.1 to about 0.5 wt %, based on the total weight of the composition. In one embodiment, in addition to the cellulose ester, EVA, and stabilizer (discussed herein), the cellulose ester composition comprises less than 5 wt %, or less than 2 wt %, in total, of any other components, based on the total weight of the composition.

[0152] In some embodiments, the cellulose ester composition comprises a maleic anhydride modified cellulose ester. It is free of VA. In some embodiments, the cellulose ester composition is free of polyetherester compounds. In some embodiments, the cellulose ester composition is free of adipate compounds. In some embodiments, the cellulose ester composition comprises 65-99 wt% of one or more cellulose esters, 1-35 wt% of one or more EVA copolymers, and less than 5 wt% in total of other components, based on the total weight of the cellulose ester composition. In some embodiments, such other components do not comprise plasticizers, polyetherester compounds, or adipate compounds. In some embodiments, the cellulose ester composition comprises a dioctyl adipate (DOA) plasticizer and no other adipate compounds.

[0153] In another aspect of the present invention, a method for producing a cellulose ester composition is provided. The method includes contacting at least one cellulose ester, at least one EVA copolymer, and optionally at least one plasticizer. The cellulose ester, the plasticizer, and the EVA copolymer are discussed herein above. In one embodiment, the cellulose ester, the EVA copolymer, and the optional plasticizer can be mixed in any order of addition.

[0154] In another aspect of the present invention, a method for producing a composition comprising the steps of: (a) at least one EVA copolymer; A method for producing a cellulose ester composition is provided, comprising mixing at least one cellulose ester and, optionally, at least one plasticizer at a time and temperature sufficient to disperse the EVA copolymer to form the cellulose ester composition. A sufficient temperature is generally defined as the flow temperature of the cellulose ester, which is about 50° C. higher than the Tg of the cellulose ester. In other embodiments, the temperature is about 80° C. higher than the Tg of the cellulose ester. In some embodiments, the temperature during mixing is limited at the upper limit by the processing temperature of the EVA copolymer and at the lower limit by the maximum use temperature of the cellulose ester composition.

[0155]

[0154] The mixing efficiency of two or more viscoelastic materials is determined by the ratio of the viscosities of the viscoelastic materials. In one aspect, for a given mixing device and shear rate range, the viscosity ratio of the dispersed phase (EVA copolymer) to the continuous phase (cellulose ester) must be within specified limits to obtain the appropriate particle size.

[0156] In some embodiments, the EVA copolymer, the cellulose ester, and optionally The mixing of the EVA copolymer, the plasticizer, and any additives can be carried out by any method known in the art that is suitable for dispersing the EVA copolymer, the plasticizer, and the additives in the cellulose ester. Examples of mixing equipment include, but are not limited to, Banbury mixers, Brabender mixers, roll mills, and extruders (single or twin screw). The shear energy during mixing is determined by the combination of equipment, blade design, rotation speed (rpm), and mixing time. The shear energy must be sufficient to disperse the EVA copolymer throughout the cellulose ester.

[0157] In some embodiments, the cellulose ester, the EVA copolymer, the plasticizer, The additives and additives can be mixed in any order during the process. In one embodiment, the cellulose ester is premixed with the EVA copolymer and / or plasticizer. The cellulose ester containing the EVA copolymer and / or plasticizer is then mixed with the additives. In another embodiment of the present invention, if a reactive impact modifier is used, the reactive impact modifier can be mixed with the cellulose ester first, and then the other ingredients are added.

[0158] The compositions of the present invention can be used as molded plastic parts or as solid plastic articles. The compositions are useful as plastics, films, fibers (including melt spun fibers and solution spun fibers), and sheets. In one embodiment, the ... films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films, films In another embodiment, the compositions of the present invention are suitable for use as films, sheeting, fibers, molded articles, medical devices, packaging, bottles, bottle caps, eyeglass frames, cutlery, disposable cutlery, cutlery handles, shelves, shelf dividers, furniture parts, electronic device housings, electronic device cases, computer monitors, printers, keyboards, pipes, toothbrush handles, automotive parts, automotive interior parts, automotive trim, signs, outdoor signs, skylights, multilayer films, thermoformed letters, siding, toys, toy parts, thermally conductive plastics, ophthalmic lenses and frames, tools, tool handles, and household products, health care products, commercial food service products, boxes, films for graphic arts applications, and plastic films for plastic glass laminates.

[0159] The cellulose ester composition can be used in the production of fibers, films, molded articles, and sheets. The cellulose ester composition is useful for forming a film. The cellulose ester composition can be formed into fibers, films, molded articles, and sheetings according to methods known in the art. Examples of possible molded articles include, without limitation, medical instruments, medical packaging, health care products, commercial food service products such as food pans, tumblers and storage boxes, bottles, food processors, blenders, and mixer bowls, household items, water bottles, crisper trays, washing machine fronts, vacuum cleaner parts, and toys. Other possible molded articles can include ophthalmic lenses and frames.

[0160] The present invention further provides one or more compositions comprising the cellulose ester compositions described herein. In some embodiments, the films and / or sheets of the present invention may be of any thickness apparent to one of ordinary skill in the art.

[0161] The present invention further provides one or more of the films and / or sheets described herein. The present invention relates to a method for forming the cellulose ester composition into one or more films and / or sheets. The method for forming the cellulose ester composition into one or more films and / or sheets can include methods known in the art. Examples of the one or more films and / or sheets of the present invention include, but are not limited to, one or more extruded films and / or sheets, one or more calendered films and / or sheets, one or more compression molded films and / or sheets, one or more solution cast films and / or sheets. Methods for producing the film and / or sheet include, but are not limited to, extrusion, calendering, compression molding, wet block processing, dry block processing, and solution casting.

[0162] The present invention further relates to shaped articles as described herein. The method of forming the composition into a molded article can include methods known in the art. Examples of molded articles of the present invention include, but are not limited to, injection molded articles, extrusion molded articles, injection blow molded articles, injection stretch blow molded articles, and extrusion blow molded articles. Methods of producing molded articles include, but are not limited to, injection molding, extrusion, injection blow molding, injection stretch blow molding, and extrusion blow molding. Methods of the present invention can include any blow molding process known in the art, such as, but not limited to, extrusion blow molding, extrusion stretch blow molding, injection blow molding, and injection stretch blow molding.

[0163]

[0162] The present invention encompasses any injection blow molding manufacturing process known in the art. A typical, but not limiting, description of an injection blow molding (IBM) manufacturing process includes: (1) melting the composition in a reciprocating screw extruder; (2) injecting the molten composition into an injection mold to form a partially cooled tube (i.e., a preform) closed at one end; (3) transferring the preform into a blow mold having the desired final shape around the preform and closing the blow mold around the preform; and (4) blowing air into the preform to stretch and expand it to fill the mold. (5) cooling the molded article; and (6) removing the article from the mold.

[0164] The present invention can be used in any injection stretch blow molding manufacturing process known in the art. Without being limited thereto, a typical description of an injection stretch blow molding (ISBM) manufacturing process involves: (1) melting the composition in a reciprocating screw extruder; (2) injecting the molten composition into an injection mold to form a partially cooled tube (i.e., a preform) closed at one end; (3) transferring the preform into a blow mold having the desired final shape around the preform and closing the blow mold around the preform; (4) stretching the preform with an internal stretch rod and blowing air into the preform to stretch and expand it to fill the mold; (5) cooling the molded article; and (6) removing the article from the mold.

[0165]

[0164] The present invention encompasses any extrusion blow molding manufacturing process known in the art. Without being limiting, a typical description of an extrusion blow molding manufacturing process involves: (1) melting the composition in an extruder; (2) extruding the molten composition through a die to form a tube of molten polymer (i.e., the parison); (3) clamping a mold having the desired final shape around the parison; (4) blowing air into the parison to stretch and expand the extrudate to fill the mold; (5) cooling the molded article; (6) removing the article from the mold; and (7) removing excess plastic (commonly called flash) from the article.

[0166] The present invention can be further illustrated by the following examples of preferred embodiments thereof, It will be understood that these examples are included for illustrative purposes only and are not intended to limit the scope of the invention unless otherwise specifically stated. EXAMPLES

[0167]

[0166] The selected cellulose ester is mixed with an EVA copolymer and / or a plasticizer. The cellulose ester compositions were prepared by mixing the cellulose ester compositions in a Leistritz 18 mm (L / D ratio of 50:1) 2-well plate. The extruder was used with a screw speed of 250 rpm and a barrel temperature of 220° C. at a throughput of 18 lbs / hour. For the CA and CAP141-20 based compositions, the barrel temperature was 230° C. The grades of the cellulose ester compositions used in the following examples are shown in Table 1 above.

[0168]

[0167] The EVA copolymers used in the examples are shown in Table 2 below.

[0168]

[0169] [Table 2]

[0170]

[0169] The examples include tests on injection molded plaques and bars. Unless otherwise specified, molding was performed on a Toyo injection molding machine with a barrel temperature of 240° C. (460° F.) and a mold temperature of 70° C. (160° F.) Unless otherwise specified, Tg, haze, light transmission, clarity, melt viscosity, and notched Izod impact strength were measured / determined as discussed below.

[0171]

[0170] ASTM standard method D: Heat the sample from -100°C at a heating rate of 20°C / min. Glass transition temperatures (Tg) were measured according to US Pat. No. 3,418,133. DSC scans of blends of materials may show multiple Tg transitions. If more than one Tg transition is found during a scan, the glass transition of the matrix is ​​defined as the highest Tg measured during the scan.

[0172]

[0171] Haze % and light transmittance were measured according to ASTM-D1003 using a 102 mm x Measurements were taken on 102 mm x 3.2 mm injection molded plaques. In the examples, where clarity ratings are given, the ratings were determined by visual inspection, with a clarity rating corresponding to a % haze of less than about 10%, a slight haze rating corresponding to a % haze of greater than about 10%, or greater than about 15% and less than about 25%, and a hazy or turbid rating corresponding to a % haze of greater than about 25%.

[0173]

[0172] Melt viscosity was measured using a Rheometrics Dynamic Analyzer (RDA II) plate-plate melt rheometer using 25 mm diameter parallel plates, a 1 mm gap, and 10% strain, using a frequency scan between 1 rad / sec and 100 rad / sec according to ASTM-D4440.

[0174]

[0173] Notched Izod impact strength tests were performed on bars at 23°C and 50% RH. After conditioning for 48 hours at 23° C., ASTM method D256 was followed on 3.2 mm thick molded bars after notching.

[0175] Example 1: CAP with and without plasticizer:

[0174] CAP grades 1 (without plasticizer (Example 1A) and 10 from Table 1 % DOA plasticizer (Example 1B)) were injection molded into 3.2 mm thick x 12.8 mm wide bars in a Toyo 110 ton injection molding machine using a barrel temperature of 240°C and a mold temperature of 70°C.

[0176] For each sample, the clarity, melt viscosity, Tg, and Izod impact strength were The material compositions and properties for Examples 1A and 1B are shown in Table 3 below.

[0176]

[0177] [Table 3]

[0178]

[0177] Table 3 shows the results of CAP482-20 (blended with and without plasticizer). ) of the properties of the cellulose ester. Inspection of the table shows that the two plastics remained clear. The CAP plastic without plasticizer had a relatively high glass transition temperature, but a low level of impact resistance. In contrast, the plasticized CAP compound had a higher level of impact strength, but a lower Tg. It would be desirable to provide a cellulose ester composition that has both the advantages of high Tg and good impact resistance.

[0179] Example 2: Blends of CE and EVA:

[0178] Different cellulose ester grades (from Table 1) were mixed at different grades and The mixture was blended with an amount of EVA copolymer and injection molded into 3.2 mm thick by 12.8 mm wide bars in a Toyo 110 ton injection molding machine using a barrel temperature of 240°C and a mold temperature of 70°C.

[0180] For each sample, the transparency, melt viscosity, Tg, and Izod impact strength were The material composition and properties for Example 2 are shown in Table 4 below.

[0180]

[0181] [Table 4]

[0182]

[0181] Considering Table 4, the CE / EVA compound is similar to the plasticized CAP compound from Table 3. It can be seen that the EVA content had a significantly higher Tg than the cellulose ester. Furthermore, for CAP482-20 (Grade 1), it is shown that when the VA content (of the EVA copolymer) was within the range of about 40% to 70% by weight, or 50 to 65% by weight, a blend with both good transparency and increased toughness (i.e., impact strength higher than 150 J / m) was obtained. This was believed to be the result of adequate interfacial adhesion, close matching of refractive index, and fine dispersion of EVA rubber particles. Furthermore, when the VA content was too high (e.g., 80%), EVA and cellulose ester were believed to be completely miscible (single composition-dependent glass transition temperature). As a result, although such a blend may be transparent, the blend had a lower Tg and less good toughness.

[0183]

[0182] Also, examining Table 4, it is clear that the VA content (of the EVA copolymer) is too low (i.e. It can also be seen that <40% resulted in formulations that were cloudy and generally more brittle, believed to be due to a lack of adequate interphase adhesion between the EVA rubber particles and the cellulose ester.

[0184] Example 3: Blends of high and low Mw CAP and EVA:

[0183] CAP grades of different ratios of molecular weight (Mw) (from Table 1) (one grade One grade has a relative viscosity of 7.4 and one grade has a relative viscosity of 2.5) was blended with different amounts of Levamelt 600 EVA copolymer and injection molded into 3.2 mm thick by 12.8 mm wide bars in a Toyo 110 ton injection molding machine using a barrel temperature of 240°C and a mold temperature of 70°C.

[0185] For each sample, the transparency, melt viscosity, Tg, and Izod impact strength were The material composition and properties for Example 3 are shown in Table 5 below.

[0185]

[0186] [Table 5]

[0187]

[0186] Considering Table 5, the lower molecular weight cellulose esters blended in the formulation It is found that this provides better fluidity (or lower melt viscosity). It is believed that blending with lower Mw cellulose esters can also provide improved color stability due to lower processing temperatures. Also, CAP482-20 and CAP482-0.5 with E It is also shown that the blends with VA had slightly lower toughness than similar CAP482-20 / EVA compositions with equivalent EVA loadings. The tensile and flexural properties (not shown) were substantially unchanged compared to a similar composition containing only CAP482-20.

[0188] Example 4: Medium Mw CAP and EVA blends:

[0187] A medium molecular weight (Mw) CAP grade with a relative viscosity of 4.26 (Table 1 from) were blended with 10 wt% of different grades of EVA copolymer and injection molded into 3.2 mm thick x 12.8 mm wide bars in a Toyo 110 ton injection molding machine using a barrel temperature of 240°C and a mold temperature of 70°C.

[0189] For each sample, the clarity, melt viscosity, Tg, and Izod impact strength were The material composition and properties for Example 4 are shown in Table 6 below.

[0189]

[0190] [Table 6]

[0191]

[0190] Inspection of Table 6 shows that the high molecular weight cellulose ester and the low molecular weight cellulose ester It is shown that a medium molecular weight cellulose ester can be used instead of a blend of esters. The table shows that the medium molecular weight cellulose ester provides good compatibility with EVA, in which case a lower VA content EVA (VA=about 28-40%) can be used and still provide toughness (as shown in 4E) that may be adequate for some applications. However, when higher toughness is required, comparing Examples 4B and 2D, and 4C and 2G, shows that using a CAP with a relative viscosity higher than 6.0 provides significantly higher impact strength and comparable Tg values ​​than using a CAP with a lower relative viscosity at the same EVA loading. Thus, in some embodiments of the present invention, cellulose ester compositions with a relative viscosity value higher than 6.0 are preferred.

[0192] Example 5: Blends of CAP, EVA, and plasticizer:

[0191] Cellulose ester grade 1 (from Table 1) was mixed with different grades of EVA. The polymers were blended with different types and amounts of plasticizers and injection molded into 3.2 mm thick x 12.8 mm wide bars in a Toyo 110 ton injection molding machine using a barrel temperature of 240° C. and a mold temperature of 70° C. DOA is dioctyl adipate and TEGEH is triethylene glycol bis-2-ethylhexanoate.

[0193] For each sample, the transparency, melt viscosity, Tg, and Izod impact strength were The material composition and properties for Example 5 are shown in Table 7 below.

[0193]

[0194] [Table 7]

[0195]

[0194] Upon review of Table 7, the addition of a plasticizer has a significant effect on the cellulose ester composition. It is shown that the flow aid can function as a flow aid that can provide a compound with a higher Tg than fully plasticized cellulose ester compounds, as well as good toughness and good flowability. It is also shown that the flow aid level must be kept lower than the normal plasticizer level for cellulose esters to provide a compound with a higher Tg than fully plasticized cellulose ester compounds, as well as good toughness and good flowability. In some cases, it has been found that certain plasticizers function in the EVA (dispersed or minor phase) rather than in the CE (continuous or major phase) as in Example 5A. As a result, the addition of plasticizer (DOA) reduces the viscosity without a significant negative effect on the glass transition temperature compared to Example 2D. It is believed that this can provide better flowability and improved color stability due to the lower processing temperature for some applications.

[0196] Example 6: Blends of CAP and EVA copolymers:

[0195] Different cellulose ester grades (from Table 1) were mixed with different grades of EVA copolymer combination and injection molded into 3.2 mm thick by 12.8 mm wide bars in a Toyo 110 ton injection molding machine using a barrel temperature of 240°C and a mold temperature of 70°C.

[0197]

[0196] The clarity, Tg, and Izod impact strength were determined for each sample. The material compositions and properties for Example 6 are shown in Table 8 below.

[0197]

[0198] [Table 8]

[0199]

[0198] Examination of Table 8 reveals that different compounds with higher and lower VA contents It is shown that blending several EVA copolymers with CAP resulted in higher impact strength (Example 6B) and had good transparency compared to only comparable amounts of EVA copolymers with higher (Example 4A) or lower (Example 4E) VA content.

[0200] Selected materials from Tables 4 and 8 were also tested using instrumentation according to ASTM-D3763. For impact testing, the specimens were injection molded into 3.2 mm thick x 102 mm x 102 mm wide plaques on a Toyo 110 ton injection molding machine using a barrel temperature of 240°C and a mold temperature of 70°C. Table 9 shows the failure modes for each sample. A ductile failure mode is assigned if the specimen plastically deforms without forming a crack that radiates more than 10 mm beyond the center of the impact point prior to failure. A brittle failure mode is assigned if the test area of ​​the specimen breaks into two or more pieces with sharp edges and little or no plastic flow is shown. Surprisingly, even at similar EVA% and average VA% content, compositions using a blend of EVA copolymers show ductile failure while compositions using a single EVA copolymer show brittle failure.

[0201]

[0200]

[0202] [Table 9]

[0203] Example 7: Haze % and Light Transmission for CAP Compositions:

[0201] CAP composition having no impact modifier (IM) or EVA copolymer, impact Haze and light transmission were determined for the CAP compositions with impact modifier and with different levels of EVA copolymer after injection molding with a 5 minute residence time at 240° C. All samples also contained 0.5% by weight of Irganox 1010. The material compositions and properties for Example 7 are shown in Table 9 below.

[0204]

[0202]

[0205] [Table 10]

[0206]

[0203] Considering Table 10, the (specified amounts) of acrylic impact modifier or EVA copolymer The results show that the addition of IM increased the haze for the CAP compositions compared to CAPs without IM or EVA, and that the CAP compositions with the EVA copolymer increased the haze less than the CAP compositions with the acrylic impact modifier. Also, the EVA copolymer had less effect on the % transmittance than the impact modifier.

[0207] The above detailed description of several aspects of the present invention will enable those skilled in the art to practice the invention. It is intended to describe various aspects of the invention in sufficient detail to enable. Other embodiments may be utilized, and changes may be made, without departing from the scope of the invention. Accordingly, the above detailed description is not to be taken in a limiting sense. The scope of the present invention is defined solely by the claims set forth in the following regular utility model application, along with the full scope of equivalents to which such claims are entitled.

[0208]

[0205] In this specification, the terms "one embodiment," "an embodiment," or "multiple embodiments" means that the associated feature or features are included in at least one aspect of the technology. Separate descriptions of "one aspect," "an aspect," or "aspects" herein do not necessarily refer to the same aspect and are not mutually exclusive unless so stated and / or apparent to one of ordinary skill in the art from the description. For example, features, steps, etc. described in one aspect may also be included in other aspects, but are not necessarily included. Thus, the present invention can encompass various combinations and / or integrations of the aspects described herein.

Claims

1. A cellulose ester composition comprising at least one cellulose ester, at least one ethylene vinyl acetate (EVA) copolymer, and optionally at least one plasticizer, The at least one cellulose ester is selected from cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB); The at least one cellulose ester has a relative viscosity of greater than 6.0 as measured for a 2 wt. % cellulose ester solution in acetone at 25° C.; and The cellulose ester composition has a Tg of at least 120°C.

2. 10. The cellulose ester composition of claim 1, wherein the composition comprises 65 to 99 weight percent of the cellulose ester, 1 to 35 weight percent of the EVA, and 0 to 15 weight percent of the plasticizer.

3. 10. The cellulose ester composition of claim 1, wherein the composition comprises 65 to 99 weight percent of the cellulose ester, 1 to 35 weight percent of the EVA, and 0 to 5 weight percent of the plasticizer.

4. 10. The cellulose ester composition of claim 1, wherein the composition comprises 70 to 97.5 weight percent of the cellulose ester, 2.5 to 30 weight percent of the EVA, and is free of plasticizers.

5. The cellulose ester composition according to any one of claims 1 to 4, wherein the cellulose ester is selected from cellulose acetate propionate (CAP) or cellulose acetate butyrate (CAB).

6. The cellulose ester composition comprises at least two different cellulose esters selected from cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB); The cellulose ester composition according to any one of claims 1 to 5, wherein at least one of the cellulose esters has a relative viscosity of greater than 6.0 as measured at 25°C for a 2 wt% cellulose ester solution in acetone; and the cellulose ester composition has a Tg of at least 120°C.

7. The cellulose ester composition of any one of claims 1 to 6, wherein the EVA has a vinyl acetate content in the range of 40 to 70 weight percent.

8. The cellulose ester composition of any of claims 1 to 7, wherein the EVA has a vinyl acetate content in the range of 50 to 65 weight percent.

9. The cellulose ester composition of any one of claims 1 to 8, wherein the EVA is a combination of at least two EVA copolymers having different vinyl acetate (VA) contents, the average VA content of the combination is in the range of 50 to 65 wt%, and the composition exhibits ductile fracture (when tested according to the examples).

10. (i) at least one cellulose ester selected from cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB); (ii) at least one ethylene vinyl acetate (EVA) copolymer; and (iii) at least one plasticizer; A cellulose ester composition comprising: The cellulose ester composition has a Tg of at least 120°C and a notched Izod impact strength of at least 200 J / m as measured according to ASTM method D256 using 3.2 mm bars at 23°C after conditioning the bars at 23°C and 50% RH for 48 hours.

11. 11. The cellulose ester composition of claim 10, wherein the cellulose ester composition has a cellulose ester continuous phase and an EVA copolymer discontinuous phase, and the plasticizer is contained in the EVA discontinuous phase.

12. 12. The cellulose ester composition of claim 10 or 11, wherein the cellulose ester composition has a Tg that differs by no more than 5% from the Tg of a similar cellulose ester composition without a plasticizer.

13. The cellulose ester composition according to any one of claims 10 to 12, wherein the cellulose ester is CAP, the plasticizer is dioctyl adipate (DOA), and the EVA has a vinyl acetate content in the range of 40 to 70 wt%.

14. The cellulose ester composition according to any one of claims 10 to 13, wherein the cellulose ester is CAP, the plasticizer is dioctyl adipate (DOA), and the EVA has a vinyl acetate content in the range of 50 to 65 wt%.

15. The cellulose ester composition according to any one of claims 1 to 14, wherein the composition further comprises at least one additive selected from the group consisting of antioxidants, heat stabilizers, release agents, antistatic agents, brighteners, colorants, plasticizers, inorganics, UV stabilizers, lubricants, nucleating agents, reinforcing fillers, glass fibers, carbon fibers, flame retardants, dyes, pigments, colorants, additional resins, and combinations thereof.

16. 16. The cellulose ester composition of any of claims 1 to 15, further comprising at least one polymer component as a blend, said polymer being selected from the group consisting of nylon; polyester; polyamide; polystyrene; other cellulose esters, cellulose ethers; polystyrene copolymers; styrene acrylonitrile copolymers; polyolefins; polyurethanes; acrylonitrile butadiene styrene copolymers; poly(methyl methacrylate); acrylic copolymers; poly(ether-imides); polyphenylene oxides; polyvinyl chloride; polyphenylene sulfide; polyphenylene sulfide / sulfones; poly(ester-carbonates); polycarbonates; polysulfones; polylactic acids; polybutylene succinates; polysulfone ethers; and poly(ether-ketones) of aromatic dihydroxy compounds; and combinations thereof.

17. 1. A method for producing a cellulose ester composition, comprising: (a) cellulose propionate (CP), cellulose butyrate (CB), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), At least one cellulose ester selected from cellulose propionate butyrate (CPB), cellulose tripropionate (CTP), or cellulose tributyrate (CTB); and (b) at least one EVA; for a time and at a temperature sufficient to disperse the EVA throughout the cellulose ester to form the composition; The method of claim 1, wherein the at least one cellulose ester has a relative viscosity of greater than 6.0 as measured at 25° C. for a solution of 2% by weight of the cellulose ester in acetone.

18. An article of manufacture comprising the cellulose ester composition of any one of claims 1 to 16.

19. 20. The article of manufacture of claim 18, wherein the article is selected from an injection molded article, an extrusion molded article, an injection blow molded article, an injection stretch blow molded article, an extrusion blow molded article comprising the cellulose ester composition of claim 1.

20. A film or sheet comprising the cellulose ester composition according to any one of claims 1 to 16.